A novel biomimetic fish-scale flow field for mass transfer enhancement and performance optimization in PEMFCs - Mi Wang; Xiuzhi Wang; Rui Wang; Zhiwei Zhang; Changwei Sun; Liwei Sun; Wenxuan Fan; Guolong Lu (Fuel, 2027)

Numerical study of ammonia combustion in a drop tube furnace: Method evaluation and burnout air modification - Tao Zhang; Rui Tan; Tianxiang Ling; Jun Chen; Weidong Fan; Qian Wang (Fuel, 2027)

Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Elements migration revealed by scientific drilling in the Anninghe fault, western Sichuan, China: Implication for seismicity in the southeastern margin of the Tibetan plateau - Qing Wei; Xuan-Hui Yang; Jia-Yong Tian; Duo-Xing Yang; Hong-Rui Fan (Journal of Asian Earth Sciences, 2026)

The effect of segment joints on the thermo-hydro-mechanical response of energy tunnels - Hu Fan; Mei Yin; Guozhu Zhang; Yi Rui; Zhengheng Gan (Computers and Geotechnics, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Synergistic operational optimizations and microbial responses stabilize filamentous-dominated continuous-flow partial denitrification-anammox at low-temperature - Jiarui Fan; Shenbin Cao; Rui Du; Yongzhen Peng (Bioresource Technology, 2026)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

USF1-mediated transcription of PARP1 contributes to sevoflurane-induced pyroptosis in perioperative neurocognitive disorders - Qingpan Zhao; Jie Fang; Bing Liang; Jianpo Zhu; Yali Zhan; Ziyan Fan; Chiyang Li; Rui Lan (Functional & Integrative Genomics, 2026)

Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Parent material modulates land use effects on soil organic carbon fractions but not inorganic carbon in subtropical red soils - Rui Jiang; Shuai Liu; Yu Zhang; Enze Xie; Beibei Fan; Fahui Jiang; Samuel Adingo; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2026)

Phytochemical profiling of undescribed triterpenoids from Cyclocarya paliurus leaves: structural elucidation and metabolic regulation potential - Yiwei Wu; Huizhen Yang; Wenjie Shangguan; Wenting Zhang; Long Chen; Rui Min; Xinrong Fan; Yindi Zhu; Xiaojie Zheng; Yin Xiong; Tunhai Xu (Phytochemistry, 2026)

Construction of CdxZn1-xS for H2 production coupled with benzyl alcohol oxidation: Regulation of electrophilic and nucleophilic properties - Mengqi Guo; Qing Xi; Jilong Qin; Jianxin Liu; Yawen Wang; Yunfang Wang; Houfen Li; Fangxia Xie; Caimei Fan; Rui Li; Jiancheng Wang (Journal of Environmental Sciences, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Fabrication of food-derived bigels beads for the co-delivery of hydrophobic and hydrophilic bioactives: insights into environmental responsiveness and release mechanisms - Rongrong Zhang; Rui Fan; Kai Qi; Jinchi Jiang; Mingzhou Yu; Yiyang Yu; Wenge Yang; Wenhui Li; Yonghong Hu (Food Research International, 2026)

A Time-Domain State-Space Iterative (TDSSI) method for seismic wave propagation in layered media under oblique incidence - Cheng Chen; Yingfang Fan; Zhiqiang Hu; Rui Pang (Computers and Geotechnics, 2026)

Addressing the protein challenge in aquaculture: Nutritional attributes, application bottlenecks and refinement strategies for single-cell protein - Jiayv Zhang; Shanfei Fu; Rui Li; Mengxue Li; Zhenni Cheng; Xiaolei Fan; Rongbo Guo; Haiqing Wang (Animal Feed Science and Technology, 2026)

Accumulation of hydrophobic bile acids mediates chronic heat stress-induced liver-gut axis injury in spotted seabass (Lateolabrax maculatus) - Fan-bo Yang; Xue-shan Li; Kai Song; Ling Wang; Rui-juan Ma; Kang-le Lu; Chun-xiao Zhang (Aquaculture, 2026)

Toward advanced management of sludge bulking: An explainable evaluation framework to quantify and improve large language model cognitive capabilities - Boyan Xu; Ning Fan; Chuankun Zhang; Guangming Xu; Huarong Yu; Huabin Zeng; Rui Tong; Kaichang Yu; Zhiguo Yuan; How Yong Ng (Water Research, 2026)

Microplastics-induced effects on membrane fouling and effluent quality in MBRs for landfill leachate treatment under long-term operation - Shijie Bian; Jingwei Yan; Timing Jiang; Huying Li; Rui Cai; Wen Li; Jingjing Shi; Fan Yang; Sha Liang; Huabo Duan; Wenbo Yu; Shushan Yuan; et al. (Waste Management, 2026)

Orogeny-driven graphitization in the Paleoproterozoic Hongqiyingzi Complex: Evidence from Yihade deposit, northern North China Block - Cun Zhang; Fan Yang; Naijie Chi; Ruiguang Wang; Nan Ma; Rui Wu (Lithos, 2026)

Photovoltaic panel arrays reshape soil erosion patterns and hydrodynamic processes on hillslopes - Nufang Fang; Rui Fan; Yue Du; Yi Zeng (Journal of Hydrology, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Exploring the mechanism of aroma production in fermented cherry juice by L. brevis LD1.0600 using flavomics and whole genome analysis - Yunfan Wang; Xuemei Zhao; Rui Li; Xilin Wang; Xinguang Fan; Yanhui Kong; Xiulian Li; Xiuli Ma; Xiangquan Zeng; Huamin Li; Wenli Liu; Yanju Li; et al. (Food Research International, 2026)

Leaching of Fe2O3 in Sauce-flavor Baijiu and its impact on trace compounds - Manjiao Chen; Weiqiang Zhou; Qianxi Jiang; Fan Zhao; Rui Zhang; Chuan Song; Zonghua Ao; Caihong Shen; Xinjun Hu; Liangliang Xie (Food Chemistry, 2026)

Tailoring ordered structures in oat flour via stepwise roasting: A strategy for concurrent enhancement of slowly digestible starch and inhibition of lipid oxidation - Jiahui Hu; Zhihong Fan; Jinjie Wei; Baoyue Liu; Rui Liu (Food Chemistry, 2026)

Synergistic effect of alkaline and heat treatment in inhibiting syneresis of CaSO₄-induced cold-set peanut protein isolate gel: Insights into structural modifications and gelation kinetics - Jing Chen; Rui Li; Zining Fan; Yu Wang; Yuntao Wang; Yanhong Bai (Food Chemistry, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Heterotrophic integration enhances structural resilience of anammox granules through extracellular polymeric substance interface remodeling - Jinyan Wang; Shenbin Cao; Xing Li; Xiaoyan Fan; Rui Du (Environmental Research, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

From diffusion limitation to ecological reassembly: Structural regulation drives functional recovery in CANDAN granules - Xinping Liu; Shenbin Cao; Xing Li; Xiaoyan Fan; Rui Du (Chemical Engineering Journal, 2026)

Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Solvent-triggered dissolution-gelation for multiscale structural densification of lignocellulosic biocomposites - Yifan Guo; He Zhang; Tongxin Bian; Xiufang Ma; Xiu Dong; Rui Fan; Wei Wei; Yun Wan; Bin Yang; Zuowan Zhou (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Multifunctional microneedle patches with sequential drug release for antimicrobial and regenerative treatment of infectious keratitis - Xiaojun Hu; Rui Liu; Qin Chen; Yunzhe Wang; Chi Zhang; Chang Liu; Yiwen Fan; Bin Kong; Xingtao Zhou; Meiyan Li (Chemical Engineering Journal, 2026)

Metagenomic insights into Thermus-mediated sulfur oxidation, nitrogen cycling, and thermoadaptation in thermophilic autotrophic denitrification bioreactors - Yuan-Yuan Xu; Xin Tan; Cheng-Cheng Dang; Zhi-Cheng Zhao; Rui Fang; Liang Fan; Nan-Qi Ren; Guo-Jun Xie; Yi-Ning Wu (Bioresource Technology, 2026)

Microbially induced hydroxyapatite improves simultaneous nitrogen and phosphorus removal in aerobic granular sludge - Fan Yang; Gonglei Wang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Jinsong Guo; Fang Fang (Bioresource Technology, 2026)

Synergistic integration of Cu-MOF and mesoporous carbon: A robust sensing interface for ultrasensitive bisphenol a monitoring in real samples - Chang Liu; Congcong Wang; Wenji Zhang; Hui Mao; Changtong Fan; Rui Zhang (Analytica Chimica Acta, 2026)

Load transfer mechanism of O-cell method for offshore foundation considering nonlinear pile-soil interface response - Rui Jiang; Yuke Wang; Zhengyu Fan; Junjing Zhang; Meiju Jiao (Marine Georesources & Geotechnology, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Breaking the “Wall”: Mechanistic insights into low-intensity ultrasound (LIU)-induced recovery of calcified CANDAN granular sludge - Shenbin Cao; Yucheng Tao; Meng Zhang; Mingsheng Jia; Xiaoyan Fan; Rui Du; Yongzhen Peng (Water Research, 2026)

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Elucidation of a novel skatole degradation pathway and key genes in Rhodococcus rhodochrous S3 - Kaihua Pan; Rui Fan; Qi Xie; Yike Lyu; Bingjie Xu; Qian Zhu; Mingliang Zhang; Qian Li; Weihao Zhu; Yanni Huang; Qing Hong; Lina Sun (Journal of Hazardous Materials, 2026)

Ecological risk assessment of caffeine in global aquatic ecosystems: From land to sea - Bo Fan; Xiaolong Guo; Baoyi Zhao; Xinyue Zhang; Yanting Mao; Baokun Lei; Rui Xu; Yuhan Yang; Yunrui Li; Junlang Deng; Yishu Deng (Journal of Hazardous Materials, 2026)

Basalt fabric functionalized with Copper/Silver nanoparticles as a salt-tolerant solar evaporator for all-weather brackish water desalination - Dilibinuer Niyazimaimaiti; Ying-Lin He; Zhuo Chen; Anand Parkash; Jincheng Wu; Ghizlane Achagri; Chun-Hong Zhou; Yuan Fan; Wen-Rui Ma; Peng-Cheng Ma; Abudukeremu Kadier (Journal of Environmental Chemical Engineering, 2026)

Synergistic utilization of ternary solid wastes for sustainable red sandstone subgrades: A simplex-centroid design approach - Weilong Song; Yunfei Han; Huayan Yao; Rui Tang; Yulu Cao; Feng Xiong; Fan Yang; Yufan Chen (Journal of Environmental Management, 2026)

Physics-validated early warning of high-energy mine tremors: Fusing multi-domain Gutenberg–Richter precursors with dynamic–static stress modelling - Jinhai Liu; Rui Xu; Kai Zhan; Shuo Fan; Zhe Li (Journal of Applied Geophysics, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Modification of Ce−Fe oxide by quenching induced trace Sn doping for accelerating chlorobenzene oxidation - Juexiu Li; Wenbo Xue; Huandan Cui; Yige Xi; Rui Zhao; Yin Liu; Zhongxian Song; Kajia Wei; Ziqiang Li; Chuanyi Fan; Kan Li; Jinping Jia (Chemical Engineering Journal, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

Low-valent cation substitution in high-entropy layered oxides inhibits Jahn–Teller distortion and accelerates sodium storage kinetics - Mengting Du; Rui Wang; Fan Wang; Lijing Yan; Quan Zong; Guoying Wei; Feifan Chang; Lu Jin; Qiaoling Kang (Chemical Engineering Journal, 2026)

Interface-engineered ZrO2@Co3O4 core-shell materials from bimetallic MOFs for enhanced room temperature NO2 sensing - Jiahui Fan; Xiaopeng Wang; Shanshan Cong; Rui Zhang; Weixin Lv; Li Li; Qingjiang Pan; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Kinetic-driven separation of ethylene from ternary mixtures by engineering the crystal size of a novel 2D metal-organic framework - Wenlei Yang; Lingyao Wang; Guangzu Xiong; Yunjia Jiang; Dong Fan; Rui-Biao Lin; Guillaume Maurin; Yuanbin Zhang; Banglin Chen (Chemical Engineering Journal, 2026)

Dynamically structured bubbles enhance energy release performance in solar-driven carbonation reaction - Chao Song; Qiang Guo; Yinshi Li; Jinbo Che; Jiabin Fang; Qiang Xu; Tao Fan; Rui Wang (Chemical Engineering Journal, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

Calcium dysregulation in neurovascular function in Alzheimer’s disease: mechanisms, therapeutic targets - Yvan Hanscom-Trofy; Andrew Gregory; Gilbert C. Morgan; Hongwei Yu; Rui Dong; Fan Fan (GeroScience, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Microbial niches and metabolism drive spatial heterogeneity of hydroxyapatite precipitation in aerobic granular sludge - Gonglei Wang; Fan Yang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Fang Fang; Jinsong Guo (Water Research, 2026)

On-chip squeezed light in the audio frequency band - Xuezhi Zhu; Yunyun Cao; Rui Liu; Yaya He; Fan Zhang; Yaqing Zhang; Shiwei Du; Meihong Wang; Xiaoshun Jiang; Xiaolong Su (Science Bulletin, 2026)

Corrigendum to “Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process” [Process Safety and Environmental Protection 203 (2025) 107862] - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2026)

Evaluation of microplastic removal performance and technologies in secondary effluent from typical sewage treatment processes using a self-developed enrichment–purification–separation-integrated device - Wenjuan Zhang; Xin Zhang; Li Fan; Siyu Wang; Shuang Ge; Rui Miao; Lei Wang; Yongtao Lv (Process Safety and Environmental Protection, 2026)

Mechanistic insights into chromium immobilization and uptake inhibition in lettuce mediated by endophyte-loaded biochar - Qizhen Liu; Jie Yuan; Ziyan Fan; Ancao Pan; Qingfeng Zhang; Rui Zhou; Nazish Jabeen Abbasi; Chao Yu; Ying Feng (Journal of Hazardous Materials, 2026)

Unveiling the neurotoxic mechanism of amino-functionalized graphene quantum dots: Mitophagy-driven ferroptosis underlies progressive anxiety-like behaviors - Lifan Fan; Yutong Liu; Nanxin Ma; Rui Wang; Wenhao Wang; Qiyue Zhang; Zhihua Ren; Xia Ning; Tingting Ku (Journal of Hazardous Materials, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Elucidating the chemical and perceptual basis of lychee-like aroma in grapes through multi-omics and molecular sensory analyses - Jingyang Wang; Chengkui Qiao; Xiucai Fan; Ying Zhang; Rui Xu; Chonghuai Liu; Lei Sun (Food Chemistry, 2026)

Balancing the modulation of soy protein structure to achieve improved texture and reduced antigenicity in soy yogurt: A practical approach of proteolytic pretreatment and lactic acid bacteria fermentation - Qiyuan Lu; Xinran Guo; Xia Fan; Benjamin K. Simpson; Wei Li; Xin Rui (Food Chemistry, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Aerobic extracellular electron transfer in Shewanella spp. - Wei Chen; Biyi Zhao; Liping Dai; Junpeng Li; Rui Bai; Fan Yang; Xudong Zhou; Jens Ulstrup; Feng Zhao; Yong Xiao (Bioresource Technology, 2026)

Identification of distributed heat sources intensities with deterministic flow fields in ventilated spaces - Yemin Liu; Xiaoliang Shao; Rui Wang; Xiaohe Tian; Huifang Fan; Jianeng Cui (Building and Environment, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Pseudofrenelopsis (Cheirolepidiaceae) from the Lower Cretaceous of northwestern China and its paleoclimatic and biogeographic significances - Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Cretaceous Research, 2026)

Two oleanane triterpenoids with a C-4 methyl substitution from Camellia oleifera Abel and their anti-inflammatory activities - Qing Li; Yijie Li; Chengqin Liang; Qijun Fan; Rui Huang; Binghai Lou; Jiangke Qin (Natural Product Research, 2026)

Spectral and structural analysis of a new lactone metabolite isolated from a mangrove endophytic fungus - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Rui Pi; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Rapid Early Miocene surface uplift of the Yarlung Tsangpo Suture Zone: Constraints from stable and clumped isotopes - Xiaohui Liu; Yimin Liu; Xudong Guo; Suoya Fan; Xiaoyu Guo; Wenxing Hao; Xingfu Huang; Xiaoming Shen; Qiuhua Ren; Ying Rao; Lin Ding; Rui Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

Tropical-origin lactic acid bacteria co-fermentation enables protein network restructuring and glucose-lipid metabolic regulation in coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Xia Fan; Xin Rui; Tao Lin; Wei Li (Innovative Food Science & Emerging Technologies, 2026)

Ascosphaeraapis LncRNA6140 promotes the infection of honeybee larvae through the milR5658-x–ATPase axis - Jianfeng Qiu; Tao Wu; Shuai zhou; Nian Fan; Genchao Gan; Zhitan Liu; Zhongmin Fu; Rui Guo; Dafu Chen (Insect Biochemistry and Molecular Biology, 2026)

Tuning the fate of radical intermediates: The pivotal role of catalyst acidity and texture in steering lignin pyrolysis pathways - Yuyang Fan; Chao Liu; Zhengxue Zhang; Shiliang Wu; Anqing Zheng; Zhaojuan Zheng; Jia Ouyang; Rui Xiao (Fuel, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Distribution profiles of 12 isoflavone monomers in Chinese soybeans from saline-alkali and ordinary soils and subsequent supercritical CO₂ extraction optimization - Zixuan Liu; Ziqian Xue; Rui Yang; Xinru Guo; Yutong Zhen; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Wide-precision planting with optimal high sowing rate improves winter wheat yield by optimizing canopy structure and radiation use - Yunchao Liu; Rui Zong; Yanli Fan; Miaomiao Qiao; Haojie Hu; Xinghui Wang; Quanqi Li (Field Crops Research, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

De novo synthesis of p-coumaric acid from fructose and carbon dioxide in chemoautotrophic Cupriavidus necator H16 - Ruohao Tang; Cunxi Dai; Caiyun Liu; Shuqi Tan; Yuanxin Ma; Yaru Fan; Rui Zeng; Xiaochun Qin (Systems Microbiology and Biomanufacturing, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Vitamin C mitigates early auditory cortical hyperexcitability and antioxidant imbalance induced by acute intermittent hypoxia - Yue Wu; Tao Li; Wanxin Cao; Rui Fan; Hailing Jiang; Jiachen Han; Furong Ma; Yan Yan (Experimental Brain Research, 2026)

Biophotocatalytic and bioelectrocatalytic strategies for methane production and oxidation: emerging pathways and perspectives - Zhenni Cheng; Xiaolei Fan; Rui Li; Kangqing Fei; Rongbo Guo; Shanfei Fu (Archives of Microbiology, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Ascosphaera apis-derived microRNA-like RNAs mediate cross-kingdom regulation of gene expression in western honeybee larvae - Xiaoxue Fan; Nian Fan; Tao Wu; Jing Kang; Jiarun Yang; Jing Tian; Xihan Luo; Dafu Chen; Jianfeng Qiu; Rui Guo (Journal of Invertebrate Pathology, 2026)

From lotus-seedpod hierarchical architecture to mussel-inspired antifouling: Synergistic design of a Janus evaporator for sustainable solar seawater purification - Siyu Huang; Xiaorui Fan; Rui Zhao; Tingting Jiang (Journal of Environmental Chemical Engineering, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Improved mitigation of reverse osmosis membrane biofouling via synergistic UV light-emitting diodes and chlorine disinfection - Yu-jia Gao; Rui-ning Wang; Shi-tong Yu; Ke-fan Cao; Xu-Cheng Cai; Yu Hong; Yun Wang; Wei E. Huang; Nozomu Ikuno; Nakata Koji; Hong-ying Hu; Yin-hu Wu (Desalination, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

A Novel ML–NWP Coupled Optimization Approach on a Reconstructed WRF Model - Hai Chu; Yuan Cao; Rui Wang; Jianming Xu; Lei Chen; Xuliang Fan; Shiqi Chen; Jianhai Guo; Junjing Wu (Journal of Meteorological Research, 2026)

Optimizing water use and biodiversity outcomes in soybean–maize strip intercropping systems - Zhendong Liu; Xiudi Shangguan; Huaiyu Mu; Jiahao Zhou; Linyao Li; Shishuo Li; Rui Zong; Xianghao Hou; Yanli Fan; Mingming Zhang; Quanqi Li (Agricultural Systems, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Reconstruction of atmospheric CO2 concentration changes during the Aalenian (Middle Jurassic) based on fossil cuticles of Ginkgoites and Czekanowskia from northwestern China - Yu Jiang; Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Occurrence and dietary risk assessments of polyethoxylated tallow amine in soybeans - Xinru Cui; Zhenjun Liu; Rui Yang; Minjie Li; Xinru Guo; Zixuan Liu; Ziqian Xue; Bei Fan; Zehua Ke; Chunmei Li; Fengzhong Wang (Journal of Hazardous Materials, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Luminescence chronology of subordinate dunes on the megadunes of the Badain Jaran Desert, North China - Tianyuan Chen; Tao Lu; Siwen Liu; Rui Yang; Zhen-Ting Wang; Yixuan Wang; Qishun Fan; Zhongping Lai (Geomorphology, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Shaking promotes the accumulation of flavor-imparting metabolites and enhances the sensory quality of spring black tea - Chunyan Fang; Rui You; Yiyun Gong; Ping Huang; Fan Huang; Wanjun Gao; Xianlin Ye; Yulong Ye (Food Chemistry, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Centrifuge modeling of static liquefaction in completely decomposed granite fill slopes - Zhun Liu; Yu Zhao; Teng Liang; Fan He; Rui Zhang; Zhuang Yan; Daosheng Ling; Liangtong Zhan; Yunmin Chen (Engineering Geology, 2026)

Molecule engineering-driven sustainable and high-performance ionic liquids lubricant on the titanium alloy surfaces and their interfacial mechanisms - Gaolu Fan; Jingyu Shan; Jingwen Guan; Ke Yang; Hongxin He; Shibo Liu; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Transient calcium crusts in PD-HAP granules: Mechanisms and self-regulatory recovery - Yu Lan; Konrad Koch; Yanling Yang; Shenbin Cao; Jiawei Ren; Xiaoyan Fan; Rui Du (Water Research, 2026)

Deformation analysis of a deep excavation with a servo control system adjacent to an existing foundation pit: A case study in Shenzhen - Liqiang Xu; Wangrong Li; Leilei Liu; Fan Wu; Zirui Fan; Rui Chen (Tunnelling and Underground Space Technology, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

YOLO-FR: An enhanced object detector for small object detection in complex scenes - Rui Fan; Renhao Jiao; Weigui Nan; Jin Dang; Zhixue Wang; Xuefeng Ge; Baiying Dong; Xiaoli Luo (Remote Sensing Applications: Society and Environment, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

Hybrid quantum-classical optimization of the resource scheduling problem - Tyler Christeson; Md Habib Ullah; Ali Arabnya; Amin Khodaei; Rui Fan (Next Research, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Quantifying the stability of influenza virus during evaporation and suspension phases using a novel bioaerosol experimental system - Jianjian Wei; Yanni Ma; Huoquan Zhu; Huishi Deng; Rui Yang; Yanshan Mai; Jianren Fan; Jie Wu (Journal of Hazardous Materials, 2026)

Exploring urban human mobility patterns and the effects of air pollution and weather conditions from a dockless bike-sharing lens - Xijie Xu; Jie Wang; Stefan Poslad; Xiaoping Rui; Guangyuan Zhang; Yonglei Fan (Journal of Cleaner Production, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Assessing the spatiotemporal dynamics of wildfire drivers in Southeast Asia: An explainable spatial machine learning framework - Lei Xia; Zhixian Yang; Yongling Yang; Liang Han; Chengwen Jia; Jie Li; Wenxuan Fan; Rui Liu (Environmental Impact Assessment Review, 2026)

A coupled strain-damage framework for rock deformation and dynamic damage under cyclic loading based on mesoscale elastoplastic elements - Haohao Zhang; Rui Chen; Yazhou Wang; Huijie Bi; Chaojun Fan; Hui Peng (Computers and Geotechnics, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

The strong quantum confinement effect of CsPbI3 quantum dots assists the subthreshold turn-on of light-emitting diodes - Mingze Liu; Min Lu; Rui Li; Junzhe Feng; Chunru Fan; Fujun Zhang; Xue Bai; Yu Zhang (Chemical Engineering Journal, 2026)

Defect-rich 3D flower-like SnS2-xSex nanostructures for ultrasensitive NO2 gas sensing at room temperature - Shanshan Cong; Pengkai Xing; Wenbo Ruan; Jiahui Fan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Qin Guo; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Unraveling mechanisms of mechanical shear stress-regulated high nitrite production in denitrification: granular structure and metagenomic evidence - Jiarui Fan; Shenbin Cao; Xiangchen Li; Yongzhen Peng; Rui Du (ENGINEERING Environment, 2026)
Partial denitrification granules (PDG) offer a novel approach to supplying nitrite (NO 2 − ) for anammox. Shear stress (τ) induced by mechanical stirring has been recognized as an effective operational strategy for enhancing mass transfer in continuous-flow PDG systems with minimal gas production. However, the effects of shear stress intensity on nitrite (NO 2 − ) accumulation, granular structure, and microbial succession remains unclear. This study established two continuously up-flow PDG systems to assess the influence of low-strength τ (0.2–0.5 Pa) and high-strength τ (1.2–1.4 Pa) on PDG performance under dynamic nitrate (NO 3 − ) loading rates (NLR). Results indicated that low-strength τ promoted the formation of 1–2 mm granules, mitigating the washout of flocs and smaller granules, and sustaining a stable nitrite production rate (NPR) of 7.7 kg N/m 3 ·d) at an NLR as high as 11.7 kg N/(m 3 ·d). In contrast, high-strength τ caused particle fragmentation and reaggregation, accompanied by the washout of sludge containing PD bacteria, leading to a lower NPR of 0.2 kg N/(m 3 ·d). Metagenomic analysis revealed that low-strength τ enhanced nitrogen-carbon metabolism, with Thauera. sp. and Thauera _phenylacetica synergistically driving NO 2 − accumulation. Although high-strength τ promoted the enrichment of Thauera (∼70%), Thauera. sp. decreased its contribution to napA and improved to nirK , whereas Thauera _phenylacetica reduced its contribution to napA , thereby constraining NO 2 − accumulation. These findings provide critical insights into optimizing shear conditions for PDG and enhance the understanding of the metagenomic mechanisms of PD.

Challenges, optimization, and delivery strategies in the heterologous expression of aldehyde dehydrogenase: therapeutic applications for acetaldehyde detoxification - Siyue Qiao; Shumei Li; Tongzheng Zhang; Fan Yang; Rui Ling Zhang; Min Li (Biotechnology Letters, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Exploring the mechanism of flavonoid amination and its potential biological implications from an in-vitro and in-vivo perspective - Pengren Zou; Celia Costas; Rui Lu; Carla Cameselle; Shiye Lin; Fan Zhang; Zhaojun Wei; Paz Otero (Critical Reviews in Food Science and Nutrition, 2026)

Joint Arctic Sea Ice Forecasting Based on Graph-Structured Spatial Modeling and Temporal Transformers - Bowen Liu; Caiping Xi; Yukai Ma; Rui Zhai; Ting Ma; Fan Yan (Journal of Marine Science and Engineering, 2026)
Rapid changes in Arctic sea ice exert significant impacts on regional climate feedbacks and high-latitude maritime activities, increasing the demand for accurate short-term forecasting of key sea ice variables. This study proposes a GraphTransformer-based framework for joint forecasting of sea ice thickness (SIT) and sea ice concentration (SIC), designed to address their strong spatiotemporal coupling under irregular Arctic Ocean geometries. A static spatial graph is constructed over effective Arctic marine grid cells, where neighborhood aggregation is applied at each time step to explicitly encode spatial correlations. A shared-parameter temporal Transformer is subsequently employed to model node-level long-range temporal dependencies and to perform direct multi-step forecasting. The model generates 14-day daily forecasts of SIT and SIC in a single forward pass. Experiments are conducted using multi-source daily data spanning from 1 January 2019 to 15 May 2025, with evaluation restricted to valid marine grid nodes. Results indicate that the proposed GraphTransformer achieves either the best or second-best performance among the compared models in multi-step forecasting accuracy. Ablation experiments further confirm the critical role of graph-based spatial encoding in enhancing spatial coherence and mitigating error propagation.

Physics-guided deep learning for geostationary satellite-based estimation of dead fuel moisture content in Southwest China - Chunquan Fan; Yiru Zhang; Rui Chen; Hongguo Zhang; Jianpeng Yin; Yanxi Li; Binbin He; Xingwen Quan (Remote Sensing of Environment, 2026)

Probabilistic mapping of high-intensity forest fire potential via time series machine learning and remote sensing-informed fire spread simulations - Rui Chen; Yiru Zhang; Yanxi Li; Marta Yebra; Chunquan Fan; Hongguo Zhang; Binbin He (Remote Sensing of Environment, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Drivers of CO2 and CH4 fluxes from shallow lakes and prediction based on climate factors under global warming - Zhentao Wu; Hui Liu; Fan Yang; Rui Ran; Huimin Yu; Haonan Xu; Danyun Chen; Geng Wang; Xiaobing Pang (Journal of Environmental Sciences, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

Synergistic Pt/Co(OH)2/PTI enhances H2O dissociation and H* adsorption for efficient alkaline hydrogen evolution - Yali Niu; Rui Yao; Shuhui Fan; Jinping Li; Guang Liu (Fuel, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Characterization of volatile compounds of irradiated and fermented cherry juice by SPME-GC–MS, SPME-GC × GC–MS and HS-GC-IMS combined with machine learning algorithm - Yunfan Wang; Xilin Wang; Rui Li; Yanhui Kong; Xiulian Li; Chengjie Fan; Xiangquan Zeng; Danliangmin Song; Huamin Li; Wenli Liu; Hansheng Gong; Xinguang Fan (Food Chemistry, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Effect of dry-blanching pretreatment and drying using radio frequency energy on the dehydration performance, structural and quality properties of tiger nuts - Mengge Li; Yingqi Tian; Liumin Fan; Dongsheng Hu; Rui Li; Shaojin Wang (Food Control, 2026)

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Self-replenishing metabolically enhanced probiotic delivery strategy to alleviate ulcerative colitis through intestinal homeostasis remodeling and aryl hydrocarbon receptor signaling activation - Rui Sun; Jiayi Chen; Jingkai Fan; Ying Wang; Xueer Wang; Yue Liu; Zhouli Wang; Tianli Yue; Yahong Yuan (Chemical Engineering Journal, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Predicting pedestrian-level melanopic illuminance from multi-source urban data with explainable machine learning - Wenjin Hong; Zhe Kong; Peng Tang; Ziqi Fan; Rui Duan; Zixuan He; Xintong Li; Xinyi Wu (Building and Environment, 2026)

Valorizing Citrus maxima peel waste into bioactive essential oil: Sustainable extraction and antimicrobial efficacy - Emmanuel Mintah Bonku; Rui-Fan Yang; Zhong-Hua Yang (Biomass and Bioenergy, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Nationwide occurrence and flux estimates of PFAS in leachate from waste-to-energy sector: an emerging reservoir linked to short-term waste storage - Xinyue Wang; Fan Chen; Yue Sun; Lanlan Fu; Rui Ma; Yue Zhi; Qian Wang; Xiaoming Wang (Water Research, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Improved drying performance and mass transfer in ginger slices using hot air-assisted radio frequency technique - Zijun Mo; Mengge Li; Jinsong Zhang; Liumin Fan; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Species-specific modeling of tree diameter at breast height using tree height and relative density with implications for remote sensing-based forest inventory - Soheil Soheili Esfahani; Fan-Rui Meng; Christopher YS Wong (Forest Ecology and Management, 2026)

Human milk oligosaccharides improve intestinal barrier integrity and immune homeostasis through the microbial metabolite butyrate - Peng Zhang; Chonghua Fan; Jiayue Li; Yalu Yan; Yumeng Zhang; Rui Zhang; Bailiang Li; Sufang Duan (Food Bioscience, 2026)

Enhancing identification confidence in non-targeted screening of emerging contaminants via an ensemble retention time prediction model: Applications in screening and ecological risk assessment - Ye Liu; Hua-Chun Liu; Tian-Hong Chen; Jian-Ping Deng; Rui-Fang Fan; Hong-Xuan Kuang; Yun-Jiang Yu (Environmental Pollution, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Health benefits of ventilation interventions to reduce fine particulate matter exposure in industrial environments - Jianchao Ma; Fan Liu; Xiaohong Zheng; Huijin Qian; Rui Qin; Hua Qian (Atmospheric Pollution Research, 2026)

Lipid Nanoparticle Development in Practice: Challenges and Collective Insights - Xiuling Lu; Sheyda Ranjbar; Fan Zhang; Yahya Choonara; Ryan M. Pearson; John Fetse; Rui He; Esraa Mohamed; Amalendu Ranjan; Muhammad Delwar Hussain; Ashraf Hatim Osman Mohamed Kheir; Chun-Wan Yen; et al. (Pharmaceutical Research, 2026)

Linking nitrite accumulation to shift in carbon utilization of denitrification: from single to composite electron donor - Qingtao Liu; Rui Du; Jiarui Fan; Yongzhen Peng (ENGINEERING Environment, 2026)

Integrated GNSS positioning and attitude determination with unscented Kalman filter - Xiangdong An; Xiaolin Meng; Yilin Xie; Fan Zhang; Liangliang Hu; Rui Shang (GPS Solutions, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

Interface states of surface water waves based on Fibonacci corrugations with mirror symmetry - Qing-Dong Hong; Lei Yang; Rui-Lin Liu; Shu-Ya Jin; Ya-Xian Fan; Zhi-Yong Tao (Wave Motion, 2026)

Gyrotropic magnetic effect in black phosphorus irradiated with bicircular light - Fangyang Zhan; Xin Jin; Da-Shuai Ma; Jing Fan; Peng Yu; Dong-Hui Xu; Rui Wang (Science Bulletin, 2026)

Mechanistic insights into low-level Cd(II)-enhanced partial denitrification: Coupled effects on granule formation and carbon–nitrogen metabolism - Shenbin Cao; Xiaoxiao Zhang; Mengmeng Zhai; Xianbao Xu; Xiaoyan Fan; Rui Du (Process Safety and Environmental Protection, 2026)

The candidate effector Bd_A04480 contributes to Botryosphaeria dothidea-induced postharvest soft rot in kiwifruit by increasing virulence and suppressing plant immunity - Hong Tan; Jinhuang Song; Juanrong Qin; Shufeng Du; Rui Yang; Xiaoqing Dong; Zhibo Zhao; Youhua Long; Rong Fan (Postharvest Biology and Technology, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Roasting oat-based paste modulates postprandial glucose and insulin sensitivity: Roles of acrylamide, texture, and starch fractions - Jiahui Hu; Zhihong Fan; Jinjie Wei; Xiyihe Peng; Qianqian Zhu; Rui Liu; Xinling Lou; Yuqing Xing (Food Research International, 2026)

Preparation of high polyphenol-low caffeine instant tea powder by exploring and regulating the changes of key functional compounds during kombucha fermentation - Rui Sun; Jingkai Fan; Yubo Zhou; Zinuo Lei; Silong Yang; Ying Wang; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Chemistry, 2026)

Comprehensive performance of iron-loaded biochar adsorption of U(VI) at an industrial scale based on life cycle assessment and economic analysis - Jia He; Zhou Shen; Yisa Li; Hao Wen; Rui Lu; Shaoli Fan; Jian Gao (Environmental Research, 2026)

Associations of outdoor artificial light at night exposure with telomere length and mitochondrial DNA copy number in children and adolescents: Examining sex-specific associations - Gaojie Fan; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; Liqin Hu; Xiaoning Lei; Youjie Wang; Mingyang Wu; et al. (Environmental Research, 2026)

Ferroptosis-mediated ocular developmental toxicity of biodegradable nanoplastics in zebrafish - Yutong Liu; Lifan Fan; Nanxin Ma; Rui Wang; Qiqi Yan; Chen Chen; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2026)

Modelling the lateral behavior of trunk-root-soil systems with representative branching patterns using a combined p-y framework - Fan He; Teng Liang; Rui Zhao; Tianfeng Zhu; Yu Zhao; Anthony Kwan Leung; Liangtong Zhan (Computers and Geotechnics, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Structural, EPS, and microbial mechanisms drive Cd(II) tolerance in partial denitrification granular sludge - Shenbin Cao; Xiaoxiao Zhang; Xing Li; Rui Du; Xiaoyan Fan; Jacek Makinia (Chemical Engineering Journal, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Inhibitory effects of various lignocellulose pretreatment byproducts on xylonic acid biosynthesis by Gluconobacter oxydans - Fan Li; Shuiping Ouyang; Rui Zhang; Xia Hua; Yong Xu; Xin Zhou (Bioresource Technology, 2026)

Mechanistic Investigation of TSPO-Mediated Dysregulation of Mitochondrial Copper Homeostasis in Microglia and its Role in Perioperative Neurocognitive Disorders - Youli Fu; Jiahe Lian; Yinglong Liu; Yongxin Liu; Zihan Xu; Haoran Fan; Yongliang Zhu; Yingxia Liang; Lina Sun; Rui Zhang (Molecular Neurobiology, 2026)

Mutant library construction and green fluorescent protein expression in a marine fungus capable of plastics biodegradation - Rui Liu; Yani Wang; Zhenjie Su; Jun Yang; Fan Fei; Rongrong Gao; Chaomin Sun (Journal of Oceanology and Limnology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

Development of potential processing technologies for germinated edible seeds and their applications in food: a comprehensive review - Gaoji Yang; Dingting Zhou; Dongsheng Hu; Liumin Fan; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Ecological functions coupled with plasmid and phage-mediated dissemination drive the global prevalence of high-risk antimicrobial resistance genes in influent - Fang Huang; Shu-Hong Gao; Yanmei Zhao; Qi Liu; Rui Gao; Zihan Dai; Jingni Xie; Bin Liang; Jinsong Liang; Lu Fan; Xin Li; Ai-Jie Wang (Water Research, 2025)

Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

Functional characterization of GmSRS14 in regulating root nodule development of soybean - Kangjun Fan; Yue Wu; Yonghua Qin; Hongzao He; Lu Lv; Gang Li; Jiao Liu; Rui Qin; Hong Liu (Journal of Plant Physiology, 2025)

Discriminating nanoparticulate and ionic silver in vivo: Organ-specific distribution and toxicological outcomes via gold-core labeling - Xiang-Rui Wang; Dingyuan Liang; Xiaoli Zhao; Ying Wang; Wen-Hong Fan (Journal of Hazardous Materials, 2025)

Enhanced capacitive deionization performance of core-shell FeHCF@NiHCF Prussian blue analogue benefited from interface effect - Zewen Fan; Wannan Wang; Jing Ren; Rui-Peng Ren; Yong-Kang Lv (Journal of Environmental Chemical Engineering, 2025)

Three-dimensional numerical study of serpentine flow-fields with vertical/lateral synergetic extended structures for PEM fuel cells - Naixiao Wang; Youliang Cheng; Xiaochao Fan; Lei Zhang; Rui Ding (Fuel, 2025)

Effect of combined treatment of pH-shifting and mild heating on gel properties of transglutaminase induced cold-set peanut protein isolate gel - Jing Chen; Si Qiu; Rui Li; Zining Fan; Yu Wang; Yuntao Wang (Food Research International, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Carbon dots-melatonin-chitosan coating to alleviate chilling injury, enhance storage quality and antioxidant capacity of yellow peaches - Kai Fan; Rui Tang; Lijing Li (Food Packaging and Shelf Life, 2025)

NepTrain and NepTrainKit: Automated active learning and visualization toolkit for neuroevolution potentials - Chengbing Chen; Yutong Li; Rui Zhao; Zhoulin Liu; Zheyong Fan; Gang Tang; Zhiyong Wang (Computer Physics Communications, 2025)

Detection of neutralizing antibody to Feline herpesvirus type 1 in cat serum - Jia Yang; Rui Mei; Kangyixin Sun; Fuqiang Xu; Fan Jia (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Efficient fabrication of micro/nanostructured porous film integrating excellent radiative cooling, robust water repellence and unidirectional moisture permeability by micro extrusion roll forming - Yunjia Cai; Yu Du; Yingying Chen; Rui Tong; Feicong Fan; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Multifunctional Au(I)-based AIEgens for the visualization and treatment of invasive fungal infections - Jiawei Zhou; Yizhi Fan; Yajuan Guan; Yiliang Qin; Dawei Liang; Shuangling Deng; Kaihui Shi; Yongyu Rui; Lei Zheng; Jing Zhang (Chemical Engineering Journal, 2025)

Mechanistic insights for DOM removal and membrane fouling mitigation: Optimizing Ferrate(VI)/AlCl₃ pretreatment and revealing the synergistic effect - Rui Zhang; Shaoyin Peng; Zhenbei Wang; Fei Qi; Chen Li; Yatao Liu; Fan Li; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; Zukhra Kadirova (Chemical Engineering Journal, 2025)

Review of structures and geodynamics of mid-ocean ridges - Jie Liao; Linfeng Liao; Mulin Zhuo; Jiarong Qing; Guangxu Wang; Yongqiang Shen; Zhuo Fan; Rui Gao (Science China Earth Sciences, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

An energy-constrained profile parameterization of shear-driven turbulence in the interior ocean - Lei Lu; Chuanyu Liu; Rui Xin Huang; Fan Wang (Frontiers in Marine Science, 2025)
This paper proposes an energy-constrained profile parameterization of both turbulent kinetic energy dissipation rate ( ϵ ) and vertical diffusivity ( κ ), for shear instability-induced turbulence that is initiated in an initial unstable layer (IUL) where the gradient Richardson number R i ∈ ( 0 , 0.25 ) . Large-eddy simulation (LES) experiments provide the data of turbulent processes originating from Kelvin-Helmholtz instability of varied initial shear conditions. The energy-constrained framework posits ϵ and κ as proportional to K a and τ – 1 , where K a represents available kinetic energy, measuring the released kinetic energy, τ denotes turbulence evolution timescale. Both are determinable by the thickness of IUL ( h 0 ), buoyancy frequency ( N 0 ), vertical shear ( S 0 ), and Richardson number ( R i 0 ) of the IUL. Notably, unlike conventional schemes that parameterize turbulent mixing for single model grid point layer by layer, the present scheme parameterizes the turbulent mixing not only for the grid point(s) of IUL, but also for all the model grid points that are within a determined vertical turbulent penetration layer, by providing a profile of diffusivity. Therefore, the scheme is termed the energy-constrained profile parameterization (EPP). EPP aligns well with the LES results and direct microstructure measurements, outperforming existing parameterizations.

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2025)

Combined effect of organic matter and antiscalants on gypsum scaling during nanofiltration - Xin He; Yulin Tang; Min Rui; Yuzhu Fan (Journal of Water Process Engineering, 2025)

Bacterial community structure and functional analysis of MBR-based wastewater treatment plants across altitudinal gradients in China - Xiangfeng Wang; Yingjie Fan; Yiwen Liu; Lingjie Liu; Yunchuan Pan; Xuebin Lu; Haiming Feng; Taihua Chen; Jian Xiong; Rui Zhang (Journal of Water Process Engineering, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

The occurrence and enrichment mechanism of indium in sphalerite from the Dachang Sn polymetallic ore field, South China: Part II. The Gaofeng deposit - Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Shi-Ni Fan; De-Feng Shi (Journal of Asian Earth Sciences, 2025)

Assessment of the effects of oligosaccharide supplementation on the structure of lactic-fermented soy protein gel and its allergenic epitopes - Xinran Guo; Xiaocui Lu; Di Yu; Xia Fan; Wei Li; Xin Rui (Food Hydrocolloids, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

Mechanistic insights into ornidazole degradation during the sulfidation and reoxidation cycling of ferrihydrite - Guangyu Li; Weijian Liu; Chenhao Wang; Zexu Zhang; Zhiruo Zhang; Rui Fan; Leyun Shi; Guorui Kong; Mengmeng Wang; Shaoping Kuang (Chemical Engineering Journal, 2025)

Optimizing electromagnetic attenuation properties via controlled dielectric polarization in Zn single-atom-decorated polymer-derived SiZnCN ceramics - Hao Deng; Yang Li; Ruihua Chen; Chao Ma; Junpeng Jiang; Daoyang Han; Bingbing Fan; Hailong Wang; Rui Zhang; Gang Shao (Chemical Engineering Journal, 2025)

Ternary eutectic solvents facilitate the production of well-dispersed chitin-glucan nanofibrils from shiitake mushrooms - Rui Zhou; Xingyu Yi; Yi Qin; Ruoyun Wu; Yang Wang; Liang Liu; Yimin Fan (Carbohydrate Polymers, 2025)

Chemical characterization of atmospheric aerosols in spring Shanghai: Formation mechanism of secondary organic aerosols on Asian dust surface - Rongjie Li; Zheng Li; Binyu Xiao; Can Wu; Rui Li; Fan Zhang; Gehui Wang (Atmospheric Research, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Characteristics and primary controls of coral reef carbonate karstification in the South China Sea since the Miocene - Yang Yang; Kefu Yu; Bin Xiong; Wei Jiang; Shendong Xu; Rui Wang; Tianlai Fan (Frontiers in Marine Science, 2025)
Coral reef karstification plays a vital role in sea-air CO 2 exchange, yet its mechanisms remain unclear. This study employs an 878.22-m coral reef sequence (dating to19.6 Ma) from Well CK2 in the Xisha Islands, South China Sea (SCS), to investigate karstification processes, including their signatures, primary controls, and implications for marine carbonate dissolution in global carbon cycling. Petrological and geochemical analyses of CK2 revel distinct karstification characteristics, including: (1) higher surface porosity 25–30%), with randomly distributed pores and fractures of variable sizes and shapes; (2) yellowish-brown to black impregnations; (3) micritic cements accompanied by well-crystallized mineral crystals, and (4) moderately well-sorted and rounded grains. Geochemical signatures show elevated 8787 Sr/ 86 Sr, Mn content, and Mn/Sr ratios, coupled with depleted δ¹³C, δ 18 O and Sr content. These features collectively indicate that karstification in CK2 was dominated by non-selective dissolution and recrystallization processes, principally occurring at the mixing zone in meteoric water systems during prolonged subaerial exposure. Karstification signatures varied across geological epochs, implying different controlling mechanisms. Late Miocene (12.6–10.2 Ma), driven by sustained sea-level fall, exhibited an extreme 87 Sr/ 86 Sr shift and severe erosion. Pleistocene (2.2–1.8, 1.1–0.89, 0.29 and 0.2 Ma), influenced by frequent sea-level fluctuations and warm, humid environments linked to glacial-interglacial cycle and Asian monsoon, displayed the highest surface porosity (15–40%, mean 25%), ochre to tawny impregnations, and micritized cements, along with negative δ¹³C-δ 18 O and elevated 87 Sr/ 86 Sr and Mn/Sr ratios. In contrast, the Middle Miocene Climatic Optimum (16.6–16 Ma) lacked typical karst characteristics but comprised of well-rounded and sorted coral gravels, suggesting reef-building organisms mediate karstification via substrate architecture. These findings demonstrate that sea-level changes and climate conditions control coral reef karstification intensity. Concurrently, dissolution during karstification may significantly modify ocean alkalinity and dissolved inorganic carbon, with potential feedback on carbon cycling in future climate scenarios.

Dynamic flexible job shop scheduling algorithm for multi-task collaborative optimization - Zeyin Guo; Lixin Wei; Xin Li; Rui Fan (Swarm and Evolutionary Computation, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

A marine fungus Alternaria alternata FB1 degrades polypropylene - Zhenjie Su; Fan Fei; Rui Liu; Chaomin Sun (Journal of Hazardous Materials, 2025)

Sustainable enzyme immobilization: Enhanced antibiotics removal via dopamine-mediated CLEAs anchoring on porous sponge carriers - Keshuai Liu; Shuxian Zhang; Lingling Yang; Xiaoxuan Fan; Xiaofei Wang; Wangyan Zhao; Rui Mai; Xiaoli Guo; Xueqin Ma; Guoning Chen (Journal of Environmental Chemical Engineering, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Understanding the combined impact of salinity and fluoride on partial denitrification: From EPS response to microbial turnover - Jinxin Fang; Shenbin Cao; Yuankun Liu; Ming Zeng; Xiaoyan Fan; Rui Du (Journal of Environmental Chemical Engineering, 2025)

Laser-structured bamboo-graphene bilayer evaporator for solar-driven, scalable, and salt-resistant water purification - Liangjuan Jiang; Rui Dang; Xiaoxue Fan; Zhaolan Wang; Shuyu Hou; Zheng Zhang; Dun Wu; Dong Wang; Zheng Cao; Chunlin Liu; Junfeng Cheng (Journal of Environmental Chemical Engineering, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Effect of radio frequency heating on structure and physicochemical properties of protein and starch based on gelatinization degree of rice flour - Dongsheng Hu; Gaoji Yang; Yingqi Tian; Mengge Li; Liumin Fan; Rui Li; Shaojin Wang (Food Research International, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Temperature-driven mineral accumulation triggers irreversible failure in a high-strength CANDAN system - Shenbin Cao; Yucheng Tao; Ziyi Cheng; Xing Li; Xiaoyan Fan; Rui Du (Chemical Engineering Journal, 2025)

Exploring the bioactive components and mechanism of Biling Weitong Granules in chronic gastric ulcer repair through network analysis and experimental verification - Rui Zhang; Jifa Fan; Zimeng Zhang; Yongxiang Wang; Wenling Dai; Jihua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Bioactivity of essential oils extracted from four varieties of Zanthoxylum bungeanum against insects and dominant spoilage fungi in Codonopsis pilosulae - Rui Feng; Zhenjia Ma; Jiali Bai; Jie Fan; Chunyu HE; Junlong Wang; Ji Zhang; Junyu Liang; Feng Zhou (South African Journal of Botany, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Developing a novel radio frequency dehydration process based on heating uniformity, drying characteristics, and product quality of white tea - Xin Ye; Jinsong Zhang; Junjie Zheng; Mengge Li; Dongsheng Hu; Liumin Fan; Rui Li; Shaojin Wang (Journal of Food Engineering, 2025)

Solar cities: Multiple-reflection within urban canyons - Fan Xu; Man Sing Wong; Rui Zhu; Ying Dang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Optimization and characterization of dummy-template molecularly imprinted polymers as sorbents for the selective recognition of the polychlorinated biphenyls - Rui Wang; Lin Liang; Wenqin Yin; Ruiying Huang; Guanhui Li; Zexiang Lu; Liwei Fan (Environmental Research, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Mechanistic Study of Jaceosidin in Regulating Secondary Inflammation After Spinal Cord Injury in Mouse by Inhibiting PKM2 Activity - Bin Dai; Zihao Fan; Rui Chen; Xuansen Weng; Run Fang (NeuroMolecular Medicine, 2025)

Desulfurization, desilication, and the separation and recovery of iron from bauxite: A review - Qinglong Fan; Shuai Yuan; Rui Han; Yanjun Li; Jiahao He; Xiaobin Ning (Minerals Engineering, 2025)

Machine learning-assisted check dam planning on the Chinese Loess Plateau - Rui Fan; Nufang Fang; Yi Zeng; Renjie Zong; Qiong Wang; Yi Zhang; Zhihua Shi (Journal of Hydrology, 2025)

One-pot synthesis of conjugated small molecules for construction of NIR fluorescence/photoacoustic dual-modal imaging nanoagents with improved photothermal/photodynamic/chemodynamic effects - Jiaqi Li; Yanqin Huang; Guice Ding; Rui Zhang; Xingfen Liu; Quli Fan; Wei Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Deciphering cadmium effects on biodegradation of triphenyl phosphate in sediments: Insights from molecular biology and computational chemistry - Dandan Li; Xiaoyu Wang; Chen Xie; Ziwu Fan; Rui Ding; Songqi Liu; Yu Chen; Kai Yu (Journal of Hazardous Materials, 2025)

Selective sulfite activation based on a non-radical reaction pathway with dominant 1O2 generation triggered by oxygen vacancies-enriched CuCo2O4 for efficient degradation of ciprofloxacin - Jinyuan Zhang; Long Cao; Jianxin Liu; Yawen Wang; Rui Li; Xiaochao Zhang; Yunfang Wang; Caimei Fan (Journal of Environmental Chemical Engineering, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Prediction and changing patterns of physicochemical properties of rice flour during radio frequency heating - Dongsheng Hu; Jiahong Yuan; Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Identification of potential natural compounds to relieve deoxynivalenol-induced intestinal damage based on bioinformatics and reverse network pharmacology - Rui Li; Kang Feng; Yu Du; Xuebin Fan; Yaqin Zhang; Chenli Wang; Jingdi Zhang; Sheraz Ahmad; Rafique Amna; Ci Liu; Ruiyan Niu; Zilong Sun (Food and Chemical Toxicology, 2025)

A state of art review on carbon, nitrogen, and phosphorus cycling and efficient utilization in paddy fields - Zeyu Zhang; Dongxing Xie; Wenhao Teng; Feng Gu; Rui Zhang; Kui Cheng; Zhuqing Liu; Ying Zhao; Fan Yang (Plant and Soil, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Biochar-loaded iron oxide as a novel electrode for the electro-Fenton degradation of sulfaquinoxaline: Performance evaluation, mechanistic insights, and toxicity transformation - Xiaowen Li; Sufang Wang; Jierong Zheng; Xin Fan; Jilong Qin; Yu Yang; Aijuan Zhou; Rui Li; Houfen Li; Xingfa Li; Xiuping Yue (Journal of Environmental Management, 2025)

“Iron -free” CdSe/ZnS quantum dots disrupt neural differentiation of embryonic stem cells via the induction of ferroptosis - Chen Chen; Rui Wang; Yutong Liu; Lifan Fan; Nanxin Ma; Qiqi Yan; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2025)

ZenSVI: An open-source software for the integrated acquisition, processing and analysis of street view imagery towards scalable urban science - Koichi Ito; Yihan Zhu; Mahmoud Abdelrahman; Xiucheng Liang; Zicheng Fan; Yujun Hou; Tianhong Zhao; Rui Ma; Kunihiko Fujiwara; Jiani Ouyang; Matias Quintana; Filip Biljecki (Computers, Environment and Urban Systems, 2025)

Multifunctional amine salt additive for enhancing the performance of perovskite and perovskite/silicon tandem solar cells - Jun Qu; Wenfeng Zhang; Yangdi Chen; Huiyao Zhao; Yanbei Wei; Rui Zhou; Hongjie Wan; Jie Deng; Dongyong Fan; Yuchen Luo; Haijin Li (Chemical Engineering Journal, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Multi-level ROS regulation to activate innate and adaptive immune therapies - Ke-Ke Feng; Cheng-Lei Li; Yi-Fan Tu; Shi-Cheng Tian; Rui Xiong; Bai-Sheng Sa; Jing-Wei Shao (Chemical Engineering Journal, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Anti-inflammatory and hepatoprotective effects of galactose-rich heteropolysaccharides from Laoshan green tea and its physicochemical properties - Shuying Lan; Rongshen Wang; Hong Gao; Mengyao Zhao; Huiting Li; Fan Liu; Rui Geng; Yuxin Wang; Xiaoxiao Liu; Chenggang Song; Wanzhong Li (Natural Product Research, 2025)

Identification of alternative splicing transcripts of Dorsal from Procambarus clarkii and their roles in innate immunity - Ying Huang; Rui Shen; Li-Fan Cui; Qian Ren (Aquaculture, 2025)

Structure of family health and its association with obesity-related eating behavior and depressive symptoms: Insights from network analysis - Junxu Lin; Zijuan Ma; Haihui Chen; Haoxian Ye; Wei Wang; Weishi Lin; Luning Yin; Rui Zhang; Dongfang Wang; Yunge Fan; Fang Fan (Appetite, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Nanoplastics and microplastics released from an enzyme-embedded biodegradable polyester during hydrolysis - Ling Ma; Zi-Yang Fan; Wen-Qian Lian; Xin-Feng Wei; Rui-Ying Bao; Wei Yang (Journal of Hazardous Materials, 2025)

Unravelling spatiotemporal heterogeneity of wildfire carbon dioxide emissions in Southeast Asia: based on a high-resolution inventory - Lei Xia; Changxu Ren; Yongling Yang; Jie Li; Wenxuan Fan; Rui Liu (Journal of Environmental Management, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Migration of acrylamide from food contact paper products and preliminary risk assessment - Wei Liu; Dajin Yang; Ziyi Wang; Rong Zhao; Sai Fan; Rui Yuan; Ruiying Tu; Daoyuan Yang; Jie Gao; Haixia Sui (Food Packaging and Shelf Life, 2025)

Understanding the role of plastic additives in the pyrolysis of plastic wastes: Impact of additives on product selectivity, kinetics, and mechanistic pathways - Letian Zhang; Nan Zhou; Linyao Ke; Yuan Zeng; Qiuhao Wu; Jiahui Zhang; Rui Liao; Liangliang Fan; Krik Cobb; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Oriented conversion of low-value heavy oil to acetylene and hydrogen using pulsed spark discharge - Hang Wang; Rui Wu; Liguang Dou; Dengke Xi; Bangdou Huang; Zhuofei Wang; Shuai Zhang; Zhe Fan; Shuai Yang; Cheng Zhang; Guoxing Chen; Tao Shao (Chemical Engineering Journal, 2025)

Single stem cell encapsulation by MnO2 doped hydrogel for robust bone regeneration - Yu Tian; Pengxia Zhang; Zhen Ma; Mengya Li; Yali Fan; Rui Guo; YanFeng Li; Yingying Zhang (Chemical Engineering Journal, 2025)

Parametric Simulation of Stress Wave Propagation Affected by High-Temperature Damage in Rocks Using a Coupled DLSM-DDA Method - Yuliang Zhang; Yiming Gu; Lifeng Fan; Gao-Feng Zhao; Fuxin Rui (Rock Mechanics and Rock Engineering, 2025)

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

The next viral pandemic—where do we stand? - Rui Fan; Qun Liang; Yanbo Sui; Yang Yang; Xingxing Yuan (Folia Microbiologica, 2025)

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

Fluoride-induced stress shapes partial denitrification granules to sustain microbial metabolism - Shenbin Cao; Jinxin Fang; Konrad Koch; Xiaoyan Fan; Hussein E. Al-Hazmi; Rui Du; George F Wells (Water Research, 2025)

Research on distributed displacement monitoring and strain inversion assessment methods for buried pipelines in fracture zones - Qunying Fan; Rui Pang; Jiajian Wang; Liang Ren; Bin Xu (Tunnelling and Underground Space Technology, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Facile isolating of chitin nanofibril from silkworm chrysalis and its potential application in structuring oil - Rui Zhou; Xinxia Li; Liang Liu; Yimin Fan (Food Hydrocolloids, 2025)

Recent advances in the impact of novel thermal technologies on gluten-free grain starches: Structures, techno-functional properties, and food applications - Dongsheng Hu; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Food Hydrocolloids, 2025)

Constructing a dual-layer PTFE nanofiltration membrane for enhanced salt solution permeability - Fuxin Qiu; Fan Liu; Rui Tian; Xutong Han; Kaikai Chen; Qinglin Huang (Desalination, 2025)

Structural characteristics and anti-tumor activities of a novel polysaccharide from Klebsiella sp. SXW12 - Xiaqing Sun; Zhenxuan Wei; Yawen Su; Rui Fang; Yizhuo Fan; Dejie Zeng; Qiankun Ding; Yaqiong Miao; Junhao Liu; Qi Sun (Carbohydrate Polymers, 2025)

Bacterial cellulose-based Pickering emulsions reinforced with silver and silica nanoparticles for advanced antibacterial and hydrophobic food packaging solutions - Qimin Chen; Fan Yang; Yalong Hou; Zhiyang Li; Di Yuan; Chao Liu; Feihong Hu; Rui Zhao; Huili Wang; Wenxia Liu; Fengshan Zhang; Qiang Wang; et al. (Carbohydrate Polymers, 2025)

The chromosome-scale genomes of two cultivated safflowers (Carthamus tinctorius) provide insights into the genetic diversity resulting from domestication - Shuo Liu; Saimire Aishan; Qiuyu Liu; Lu Lv; Kang Ma; Kangjun Fan; Kehui Zhang; Yonghua Qin; Gang Li; Xueli Hu; Zunhong Hu; Junwei He; et al. (Theoretical and Applied Genetics, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Responses of plant biomass allocation to changed precipitation timing in a semi-arid steppe - Huiru Jin; Chunkun Fan; Hongyan Zhu; Yuxian Zhang; Rui Xiao; Zhongling Yang (Plant and Soil, 2025)

Effects of the interspecific competition between Eichhornia crassipes and Alternanthera philoxeroides and the additional impact of their biological control agents: relevance for aquatic weed management - Zhenhuan He; Xiaoliang Zhang; Shufeng Fan; Rui Chen; Jieyu Sun; Fei Ma; Peidong Zhao; Jinfu Liu; Haiyan Zhang; Chunhua Liu (Hydrobiologia, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Effective evaluation of greenhouse gases (GHGs) emissions from anoxic/oxic (A/O) process of regenerated papermaking wastewater treatment through hybrid deep learning techniques: Leveraging the critical role of water quality indicators - Xing Fan; Guoqiang Niu; Rui Liu; Jianwu Qin; Xiaohui Yi; Jun Tu; Xiaoyong Li; Mingzhi Huang (Journal of Environmental Management, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Determination of five alternaria toxins in peppermint by dispersive solid-phase extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry based on MOF-808-TFA - Minhai Liu; Yan Zhang; Rui Cheng; Ting Tan; Lan Guo; Fan Liu; Yiqun Wan (Food Chemistry, 2025)

NIR-activatable proenzyme DSF/CuS@M for synergistic in situ chemotherapy/CDT/PTT/cuproptosis-based antitumor therapy - Lushuang Xu; Qinyue Chen; Yangwei Qian; Jin Wang; Chenxi Wang; Rui Fan; Jia-Wei Shen; Qiying Shen (Chemical Engineering Journal, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

Robust lubricity and multifunctional water-based lubrication system induced by ionic liquids with its interfacial self-assembly behavior and unique hydration structure - Mengyao Liu; Yingying Yao; Bingyu Tian; Kun Cui; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2025)

Temporal evolution, tectonic exhumation and preservation potential of the giant Zaozigou Au deposit in West Qinling Orogen, China - Fan Yang; Gilby Jepson; Leon Bagas; Jiarun Tu; Cun Zhang; Rui Zhu; Junfeng Shen (Science China Earth Sciences, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Effect of Litter Changes on Soil Microbial Community and Respiration in a Coniferous–Broadleaf Mixed Forest - Ziqiang Shi; Chunkun Fan; Shiming Zhao; Rui Xiao; Renhui Miao; Zhongling Yang; Shiqiang Wan (Ecosystems, 2025)

Dramatical variation in rill erosion resistance during two-year continuous straw incorporation on sloping farmland - Yi Zhang; Hanyu Zhang; Jingjiang Li; Xia Li; Yingying Zhang; Yi Zeng; Wei Dai; Rui Fan; Qianjin Liu; Nufang Fang (Agriculture, Ecosystems & Environment, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Molecular disruptions in microalgae caused by Acidithiobacillus ferrooxidans: Photosynthesis, oxidative stress, and energy metabolism in acid mine drainage - Meichen Wang; Zhengbo Yue; Rui Deng; Zhixiang She; Lu Zhang; Fan Yang; Jin Wang (Water Research, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Facile synthesis of high-swelling cyclodextrin polymer for sustainable water purification - Kai Zhang; Yu Dai; Rui Liu; Yongli Shi; Guofei Dai; Fan Xia; Xiaojin Zhang (Journal of Hazardous Materials, 2025)

Biochar chemical-looping gasification for hydrogen-rich syngas production in solid-solid reaction: O, H and CaO of carbide slag effect NiFe2O4 oxygen carrier - Chenlong Liu; Wenqiang Tang; Xuechen zhang; Siddig Abuelgasim; Chenghua Xu; Rui Liu; Hengyi Xie; Fan Jiang (Journal of Environmental Management, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A physics-data-driven method for predicting surface and building settlement induced by tunnel construction - You Wang; Qianjun Fan; Fang Dai; Rui Wang; Bosong Ding (Computers and Geotechnics, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Effect of torrefaction pretreatment on catalytic pyrolysis of bagasse: A study on torrefaction method and atmosphere - Rui Liao; Xiaojie Tian; Liangliang Fan; Hui Li; Yuan Zeng; Linyao Ke; Qiuhao Wu; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

A photoswitchable phase-reversible gel engine for systemic redox homeostasis remodeling and on-demand chemodynamic immunotherapy with sustainable immunostimulation - Minghao Sun; Weiwei Liu; Yuanyuan Ma; Pengfei Ni; Wenjing Yao; Yingjie Xu; Rui Bao; Jue Wang; Fei Xiong; Xihe Kuang; Teng Zhang; Xiaochen Zhang; et al. (Chemical Engineering Journal, 2025)

Hydrogen generation via chemical looping water splitting over modified pyrite cinder as oxygen carrier fueled by biomass pyrolysis gas - Fan Yin; Liyan Sun; Rui Xiao (Chemical Engineering Journal, 2025)

An eco-friendly catalytic pretreatment using recyclable CuFeO2 catalyst for enhancing the production of bio-based ethanol and jet fuel - Rui Zhang; Can Zhu; Yu Jiang; Yuming Ni; Nan Huang; Wanyun Tang; Minghui Fan; Quanxin Li (Biomass and Bioenergy, 2025)

Sodium-glucose cotransporter 2 inhibitors and contrast-induced nephropathy risk: a meta-analysis - Gang Fan; Lin Lin; Hong Zuo; Rui Yan; Chao Xu (European Journal of Clinical Pharmacology, 2025)

Ammonia-oxidizing microorganisms overwhelm denitrifiers in determining the efficacy of DMPP in upland soils - Jilin Lei; Donghan Yang; Yingying Sun; Saihong Wang; Qianyi Fan; Junhui Yin; Rui Liu; Qing Chen (Applied Soil Ecology, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Molecular disturbances and thyroid gland dysfunction in rats chronically exposed to a high dose of NaAsO₂: Insights from proteomic and phosphoproteomic analyses - Jie Xiang; Lili Fan; Hui Li; Qian Song; Ying Jin; Rui He; Xueli Pan; Dapeng Wang (Journal of Hazardous Materials, 2025)

Relative contributions of climate and grazing to forage supply in the Yellow River source area - Suizi Wang; Jiangwen Fan; Miaomiao Wang; Rui Tang; Nan-Ji Jiang (Journal of Environmental Management, 2025)

The role of sulfur cycle in new particle formation: Cycloaddition reaction of SO3 to H2S - Haijie Zhang; Wei Wang; Liang Fan; Junling Li; Yanqin Ren; Hong Li; Rui Gao; Yisheng Xu (Journal of Environmental Sciences, 2025)

A gamma-ray imaging method for multiple radionuclides and low-activity radioactive sources - Donghai Fan; Rui Wu; Dengke Wei; Yingrui Li; Tingting Tan; Gangqiang Zha (Journal of Environmental Radioactivity, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Lung proteomic and metabolomic changes induced by carbon black nanoparticles and high humidity in a mouse asthma model - Rui Deng; Mingpu Wang; Kian Fan Chung; Ya Zhu (Environmental Pollution, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Designing MXene hydrogels for flexible and high-efficiency electromagnetic wave absorption using digital light processing 3D printing - Yilin Liu; Wenzhao Geng; Linan Wang; Hailong Wang; Rui Zhang; Di Lan; Bingbing Fan (Chemical Engineering Journal, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Design of a prismatic CERMET megawatt gas-cooled reactor(PC-MGCR) for deep space exploration - Yuhan Fan; Rui Yan; Guifeng Zhu; Liang Chen; Naiwen Zhang; Yang Zou (Annals of Nuclear Energy, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Experimental investigation of natural gas leakage and dispersion characteristics in utility tunnels under the effects of real facility layout and forced ventilation - Jitao Cai; Jiansong Wu; Yuhang Wang; Chen Fan; Rui Zhou (Tunnelling and Underground Space Technology, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Extraction of phenolic acids and tetramethylpyrazine in Shanxi aged vinegar base on vortex-assisted liquid-liquid microextraction-hydrophobic deep eutectic solvent: COSMO-RS calculations and ANN-GA optimization - Baoqing Bai; Siyuan Meng; Yanli Guo; Ziqing Zhang; Rui Chen; Tao Bo; Jinhua Zhang; Sanhong Fan; Yukun Yang (Food Chemistry, 2025)

Effect of the Hofmeister series anion salts on the ice recrystallization inhibition activity of tamarind seed polysaccharide - Xianbao Sun; Shihao Dai; Rui Guo; Taijie Zhan; Fan Xie; Yuxing Kou; Xuan Ma; Yinan Chen; Lihua Song; Hui Zhang; Lu Ren; Chunmei Yuan; et al. (Food Hydrocolloids, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

Low-resource dynamic loading identification of nonlinear system using pretraining - Rui Zhu; Weixuan Yuan; Qingguo Fei; Qiang Chen; Gang Fan; Stefano Marchesiello; Dario Anastasio (Engineering Structures, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Synchronously enhanced breakdown strength and energy storage ability of cellulose acetate flexible films via introducing ultra-low content of carbonized polymer dots - Rui Luo; Fan Zhang; Jing-hui Yang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Surface-Enhanced Raman Scattering (SERS)-based biosensors for advanced extracellular vesicle detection: A review - Rui Fan; Siting Chen; Fei Lan; Wenbin Li; Yitong Zhu; Lifeng Zhang; Ye Zhang; Ling Li (Analytica Chimica Acta, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Strain-level multidrug-resistant pathogenic bacteria in urban wastewater treatment plants: Transmission, source tracking and evolution - Yanmei Zhao; Lu Fan; Shu-Hong Gao; Fang Huang; Zelin Lei; Wenxiu Wang; Rui Gao; Zihan Dai; Qian Li; Bin Liang; Aijie Wang (Water Research, 2024)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Crustal-derived versus mantle-derived carbonatites - Ben-Xun Su; Shi-Ying Wang; Jing Wang; Hong-Rui Fan (Lithos, 2024)

Evidence that cadmium aggravate the toxicity of triphenyl phosphate in aquatic sediments to Corbicula fluminea - Dandan Li; Chen Xie; Ziwu Fan; Rui Ding; Xiaoyu Wang; Yipeng Liao (Journal of Hazardous Materials, 2024)

Efficient biodegradation of poly(butylene adipate-co-terephthalate) in mild temperature by cutinases derived from a marine fungus - Fan Fei; Zhenjie Su; Rui Liu; Rongrong Gao; Chaomin Sun (Journal of Hazardous Materials, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Occurrence and distribution of phytic acid and its degradation products in soybeans in China: Analytical challenges - Jiayue Chen; Zhenjun Liu; Xinru Cui; Rui Yang; Xinru Guo; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Microwave pyrolysis of Choerospondias axillaris seeds with their derived biochar for comprehensive utilization of the biomass - Ruolan Zhou; Xiaojie Tian; Xiaofei Wang; Yuan Zeng; Linyao Ke; Qiuhao Wu; Rui Liao; Roger Ruan; Liangliang Fan; Yunpu Wang (Chemical Engineering Journal, 2024)

Sample-to-answer point-of-care testing platform for quantitative detection of small molecules in blood using a smartphone-and microfluidic-based nanoplasmonic biosensor - Hongli Fan; Rui Li; Youqian Chen; Qiang Da; Chenchen Xiong; Yiyi Zhang; Zhiguo Qin; Gang L. Liu; Liping Huang (Chemical Engineering Journal, 2024)

Activated carbon fiber loaded nano zero-valent iron for Microcystis aeruginosa removal: Performance and mechanisms - Guoming Zeng; Dong Liang; Xuanhao Fan; Yu He; Rui Zhang; Xiaoling Lei; Haoxuan Wei; Da Sun (Bioresource Technology, 2024)

Sirtuins as Potential Targets for Neuroprotection: Mechanisms of Early Brain Injury Induced by Subarachnoid Hemorrhage - Kunqian Lei; Rui Wu; Jin Wang; Xianze Lei; Erxiong Zhou; Ruiming Fan; Lei Gong (Translational Stroke Research, 2024)
Subarachnoid hemorrhage (SAH) is a prevalent cerebrovascular disease with significant global mortality and morbidity rates. Despite advancements in pharmacological and surgical approaches, the quality of life for SAH survivors has not shown substantial improvement. Traditionally, vasospasm has been considered a primary contributor to death and disability following SAH, but anti-vasospastic therapies have not demonstrated significant benefits for SAH patients' prognosis. Emerging studies suggest that early brain injury (EBI) may play a crucial role in influencing SAH prognosis. Sirtuins (SIRTs), a group of NAD + -dependent deacylases comprising seven mammalian family members (SIRT1 to SIRT7), have been found to be involved in neural tissue development, plasticity, and aging. They also exhibit vital functions in various central nervous system (CNS) processes, including cognition, pain perception, mood, behavior, sleep, and circadian rhythms. Extensive research has uncovered the multifaceted roles of SIRTs in CNS disorders, offering insights into potential markers for pathological processes and promising therapeutic targets (such as SIRT1 activators and SIRT2 inhibitors). In this article, we provide an overview of recent research progress on the application of SIRTs in subarachnoid hemorrhage and explore their underlying mechanisms of action.

Watershed-oriented and multifactor-integrated identification and hazard evaluation of debris-flow-prone watersheds in Danba, China - Xiaojun Luo; Mingyue Hou; Jiayin Fan; Rui Li; Jiawen Bao; Chenhao Li; Hang Li; Jie Deng (Landslides, 2024)

Rhizosphere Ecological Characteristics of Trifolium repens L. under Cadmium Stress: with Focus on the Spatial Distribution Pattern of Enzyme Activity - Chenxi Zhang; Haibo Li; Fan Mo; Mingshuai Wang; Yaran Bai; Haotian Ma; Bingqian Gao; Rui Wang (Journal of Soil Science and Plant Nutrition, 2024)

Fracture prediction method for deep coalbed methane reservoirs based on seismic texture attributes - Bing Zhang; Xue-mei Qi; Ya-ping Huang; Hai-feng Zhang; Fan-rui Huang (Applied Geophysics, 2024)

Optimization of Preparation Technology for PET-Based Carbon Dots by Response Surface Method and Its Application - Chaohui Ma; Gaoling Jin; Puzhen He; Chuanjiang Tang; Linhan Bing; Botong Liu; Hanjiang Huang; Yu Fan; Rui Wang; Jianfei Wei (Journal of Fluorescence, 2024)

Anxiety caused by chronic exposure to methylisothiazolinone in zebrafish: Behavioral analysis, brain histology and gene responses - Rui Li; Jiangbo Qu; Xinyuan Hu; Tianjia Song; Junxia Hu; Xuesong Fan; Yuanqing Zhang; Weili Xia; Tiangui Yu (Chemosphere, 2024)

A novel AMSR2 retrieval algorithm for global C-band vegetation optical depth and soil moisture (AMSR2 IB): Parameters' calibration, evaluation and inter-comparison - Mengjia Wang; Philippe Ciais; Frédéric Frappart; Shengli Tao; Lei Fan; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; Jean-Pierre Wigneron (Remote Sensing of Environment, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

A miniaturized microfluidic nanoplasmonic sensor with cavity reflection enhancement for ultrasensitive molecular interaction analysis - Hongli Fan; Mingqian Chen; Rui Li; Youqian Chen; Shaoqi Zeng; Wenjun Hu; Gang L. Liu; Chunmeng Sun; Liping Huang (Chemical Engineering Journal, 2024)

Cu2WS4 with high-exposure {0 0 1} surfaces promotes efficient charge separation in ZnIn2S4 - Rui Li; Shuangjun Li; Luyang Zuo; Xiangping Xiao; Huitao Fan; Bo Li; Liya Wang (Chemical Engineering Journal, 2024)

Construction of a highly ordered SiC nanofiber@C fiber heterojunction hybrid with a fuzzy grass-like structure for enhanced microwave absorbing performance - Wenzhao Geng; Yilin Liu; Haoyuan Lei; Limeng Song; Hailong Wang; Gang Shao; Yanqiu Zhu; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Crustal anatectic origin of the pegmatitic carbonate rocks in the Proterozoic Highland Complex, Sri Lanka - Ben-Xun Su; Shi-Ying Wang; P. L. Dharmapriya; Jing Wang; Sanjeewa P. K. Malaviarachchi; Kui-Feng Yang; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2024)

Prolonged exposure to NaAsO2 induces thyroid dysfunction and inflammatory injury in Sprague‒Dawley rats, involvement of NLRP3 inflammasome‒mediated pyroptosis - Lili Fan; Qian Song; Ying Jin; Rui He; Heng Diao; Peng Luo; Dapeng Wang (Archives of Toxicology, 2024)

Senescent endothelial cells: a potential target for diabetic retinopathy - Ying-Lu Liao; Yi-Fan Fang; Jia-Xing Sun; Guo-Rui Dou (Angiogenesis, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Atmospheric brown carbon in China haze is dominated by secondary formation - Xiaodi Liu; Can Wu; Zheng Li; Rongjie Li; Fanglin Wang; Shaojun Lv; Rui Li; Fan Zhang; Haoyang Wang; Chenlong Liang; Lei Zhang; Gehui Wang (Science of The Total Environment, 2024)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

In vitro digestion and functional properties of bovine β-casein: A comparison between adults and infants - Xiaoqian Chen; Rui Fan; Xinyu Wang; Lina Zhang; Caiyun Wang; Zhanqun Hou; Chun Li; Libo Liu; Jian He (Food Research International, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situ sonodynamic antimicrobial therapy for biomedical implants - Lei Ji; Yun Xue; Dong Wang; Yu Fan; You Zhou; Chuanan Shen; Rui Shi; Jiatao Zhang (Chemical Engineering Journal, 2024)

Understanding Partial Denitrification-hydroxyapatite (PD-HAP) coupled granules to enhance process stability and phosphorus removal by investigating the size effect of granules - Jinxin Fang; Yu Lan; Rui Du; Jiawei Ren; Xing Li; Xiaoyan Fan; Shenbin Cao (Chemical Engineering Journal, 2024)

Outstanding comprehensive energy storage performances in multiscale synergistic regulation-engineered (Bi0.5Na0.5)TiO3-based multilayer ceramics - Hang Xie; Zhenhao Fan; Linjing Liu; Shuai Yang; Qiangwei Kou; Rui Lv; Jian Dai; Hongliang Du; Yunfei Chang; Fei Li (Chemical Engineering Journal, 2024)

Predicting the impacts of climate change on the geographic distribution of moso bamboo in China based on biomod2 model - Rui Gu; Songpo Wei; Jiarui Li; Shihui Zheng; Zhiteng Li; Guanglu Liu; Shaohui Fan (European Journal of Forest Research, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Plastic particles and fluorescent brightener co-modify Chlorella pyrenoidosa photosynthesis and a machine learning approach predict algae growth - Yaodan Dai; Zhi Guo; Xingpan Guo; Rui Deng; Lele Li; Ting Fan; Kangping Cui; Tao Pan (Journal of Hazardous Materials, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Biofilms recall versatile capability of anammox integrating with heterotrophs and advances in application for wastewater treatment: A critical review - Rui Du; Fangyu Chang; Jiarui Fan; Duanyuan Xu; Shenbin Cao; Yongzhen Peng; Harald Horn (Chemical Engineering Journal, 2024)

Interface engineering of polymer composite films for high-temperature capacitive energy storage - Xiang Yu; Rui Yang; Wenqi Zhang; Xiao Yang; Chuang Ma; Kaixuan Sun; Guangyi Shen; Fangcheng Lv; Sidi Fan (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

OsSPL11 positively regulates grain size by activating the expression of GW5L in rice - Xinhai Zeng; Kai Fan; Yu Shi; Rui Chen; Wanyu Liu; Xin Wang; Guixiang Ye; Wenxiong Lin; Zhaowei Li (Plant Cell Reports, 2024)

Changing Drip Fertigation Strategy to Decrease Greenhouse Agroecosystem Soil Nitrate Residue and Improve Tomato Production in Northwest of China - You Wu; Jiale Zhang; Shicheng Yan; Wei Si; Rui Liu; Jianhua Yang; Zhenxin Qiu; Junliang Fan; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2024)

How territorial function determines CO2 emissions in China: An approach of spatial dimension - Jie Fan; Zheng Wang; Daojing Zhou; Rui Guo; Dong Chen; Baoyin Liu; Hanchu Liu; Qin Qiao; Jianxiong Wu (Journal of Geographical Sciences, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Strong controlling effect of stress evolution on the 2022 Ms5.0 Honghe earthquake sequence - Ye Zhu; Wenjie Fan; Yingfeng Ji; Weiling Zhu; Lili Feng; Rui Qu (Tectonophysics, 2024)

In situ real-time pathway to study the polyethylene long-term degradation process by a marine fungus through confocal Raman quantitative imaging - Wanying He; Rui Liu; Fan Fei; Shichuan Xi; Zengfeng Du; Zhendong Luan; Chaomin Sun; Xin Zhang (Science of The Total Environment, 2024)

Multi-medium residues and ecological risk of herbicides in a typical agricultural watershed of the Mollisols region, Northeast China - Hanqiang Liu; Rui Li; Wenyou Hu; Le Jian; Biao Huang; Ya'nan Fan; Yongcun Zhao; Hongyan Zhang; Khalid Saifullah Khan (Science of The Total Environment, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Exploring the neural correlates of fat taste perception and discrimination: Insights from electroencephalogram analysis - Tianyi Yang; Peng Zhang; Jin Hu; Wei Xu; Wei Jiang; Rui Feng; Yajun Lou; Xiaofei Jin; Zhiyu Qian; Fan Gao; Keqiang Gao; Rui Liu; et al. (Food Chemistry, 2024)

Dynamics changes in metabolites and pancreatic lipase inhibitory ability of instant dark tea during liquid-state fermentation by Aspergillus niger - Haoran Sun; Ranqin Fan; Rui Fang; Shanshan Shen; Yu Wang; Jialin Fu; Rui Hou; Runchen Sun; Shinuo Bao; Qi Chen; Pengxiang Yue; Xueling Gao (Food Chemistry, 2024)

Lung microbiota participated in fibrous microplastics (MPs) aggravating OVA-induced asthma disease in mice - Qian Wu; Rui Li; Yifei You; Wei Cheng; Yan Li; Yan Feng; Yuqin Fan; Yan Wang (Food and Chemical Toxicology, 2024)

Fe2O3@ZrO2 catalyst derived from MOF-on-MOF for direct CO2 hydrogenation to light olefins - Fan Xu; Xin Meng; Rui Zhao; Daoming Jin; Wenhua Dai; Dandan Yang; Zhong Xin (Chemical Engineering Journal, 2024)

Adaptation of freshwater partial Denitrification/Anammox (PD/A) granules to low-salt conditions: Process performance and metabolic insights - Qingliang Su; Jiawei Zhang; Ming Zeng; Rui Du; Xiaoyan Fan; Shenbin Cao (Chemical Engineering Journal, 2024)

Association Between Multiple Metal(loid)s Exposure and Blood Lipid Levels: Evidence from a Cross-Sectional Study of Southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Rui Su; Shaoqi Rao; Yanhui Zhu; Jie Xie; Chang Feng; Guangqin Fan (Biological Trace Element Research, 2024)

Isolation, identification and transcriptome analysis of triadimefon-degrading strain Enterobacter hormaechei TY18 - Yan Wang; Qi Guan; Wenhui Jiao; Jiangbo Li; Rui Zhao; Xiqian Zhang; Weixin Fan; Chunwei Wang (Biodegradation, 2024)

The concentrations and behavior of classic phthalates and emerging phthalate alternatives in different environmental matrices and their biological health risks - Lele Li; Zhi Guo; Rui Deng; Ting Fan; Dazhuang Dong; Yaodan Dai; Chenxuan Li (Environmental Science and Pollution Research, 2024)

Stackelberg game-based method towards carbon-economy equilibrium for the prefabricated construction supply planning: A case study from China - Mengyuan Zhu; Yu Wang; Rui Liu; Lurong Fan (Sustainable Cities and Society, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Super Fe3+ competing ability, high biocompatibility, and mild antibacterial carbon dots for food preservation - Fangchao Cui; Rongsen Fan; Dangfeng Wang; Likun Ren; Qianqian Wang; Yuqiong Meng; Rui Ma; Shulin Wang; Zhiteng Liu; Xuepeng Li; Tingting Li; Jianrong Li (Chemical Engineering Journal, 2024)

Magnetic media synergistic carbon fiber@Ni/NiO composites for high-efficiency electromagnetic wave absorption - Dalong Tan; Qian Wang; Mengru Li; Limeng Song; Fan Zhang; Zhiyu Min; Hailong Wang; Yanqiu Zhu; Rui Zhang; Di Lan; Bingbing Fan (Chemical Engineering Journal, 2024)

Genome-wide identification of the MED25 BINDING RING-H2 PROTEIN gene family in foxtail millet (Setaria italica L.) and the role of SiMBR2 in resistance to abiotic stress in Arabidopsis - Yimin Fan; Yue Guo; Haiying Zhang; Rui Han; Pu Yang; Zhen Liang; Lizhen Zhang; Ben Zhang (Planta, 2024)

Groundwater spring potential mapping: Assessment the contribution of hydrogeological factors - Rui Zhao; Chenchen Fan; Alireza Arabameri; M Santosh; Lal Mohammad; Ismail Mondal (Advances in Space Research, 2024)

Qualitative classification of waste garments for textile recycling based on machine vision and attention mechanisms - Rui Tian; Ziqi Lv; Yuhan Fan; Tianyu Wang; Meijie Sun; Zhiqiang Xu (Waste Management, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

Changes in the lithosphere, atmosphere, and ionosphere before and during the Mw = 7.7 Jamaica 2020 earthquake - Dedalo Marchetti; Kaiguang Zhu; Alessandro Piscini; Essam Ghamry; Xuhui Shen; Rui Yan; Xiaodan He; Ting Wang; Wenqi Chen; Jiami Wen; Yiqun Zhang; Yuqi Cheng; et al. (Remote Sensing of Environment, 2024)

Experimental study on long-term impermeability of recycled aggregate concrete mixed with crystalline admixture and waste glass powder - Yankai Wang; Xiang Fan; Rui Wu; Hang Lin; Wenwen Feng (Journal of Cleaner Production, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

Comparison of a novel GtfB-type 4,6-α-glucanotransferase from Fructilactobacillus sanfranciscensis Gs2 for converting starch in the gelatinized and granular systems - Jingjing Dong; Yanli Wang; Xiaoxiao Li; Ying Chen; Rui Fan; Nana Wang; Zhengyu Jin; Yuxiang Bai (Food Bioscience, 2024)

Bio-adhesives derived from sewage sludge via hydrothermal carbonization: Influence of aqueous phase recycling - Zhi-Xiang Xu; Rui Dou; Fan Gao; Yong-Xing Chen; Li-Jian Leng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Photoactive cationic conjugated microporous polymers containing pyrimidine with an ‘adsorption-kill’ antibacterial strategy for infected wound healing - Ga Liu; Shengfei Bao; Jiahao Shi; Chunyu Xie; Fuying Liao; Lingshuang Wang; Fan Zheng; Rui L. Reis; Subhas C. Kundu; Bo Xiao; Xiao Yang; Lian Duan (Chemical Engineering Journal, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Influence of ion size on the charge storage mechanism of MXenes: a combination of experimental and computational study - Huiwen Wan; Rui Wang; Huiyang Fan; Hongbo Gao; Yucheng Chen; Zhu Liu (Waste Disposal & Sustainable Energy, 2024)

Impacts of permafrost degradation on streamflow in the northern Himalayas - Linfeng Fan; Fang Ji; Xingxing Kuang; Zhilin Guo; Rui Zhang; Chunmiao Zheng (Science China Earth Sciences, 2024)

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

Assessing watershed-scale impacts of best management practices and elevated atmospheric carbon dioxide concentrations on water yield - Xiaoyu Kang; Junyu Qi; Charles P.-A. Bourque; Sheng Li; Chuan Jin; Fan-Rui Meng (Science of The Total Environment, 2024)

Comprehensive utilization for hydrothermal conversion products of food waste - Rui Bao; Shuzhong Wang; Jiaqi Feng; Kai Liu; Hui Liu; Fan Zhang; Yuanwang Duan; Zicheng Li; Jianqiao Yang (Journal of Cleaner Production, 2024)

A novel MnCoOx@TiO2 double–wall nanocages derived from Prussian blue analogue for NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Fuel, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Myofibrillar proteins’ intermolecular interaction weakening and degradation: Are they mainly responsible for the tenderization of meat containing l–arginine, l–lysine, or/and NaCl? - Xiaokang Fan; Xun Gao; Rui Li; Dongmei Pan; Cunliu Zhou (Food Chemistry, 2024)

High-efficiency preparation of starch nanocrystals with small size and high crystallinity by ethanol-acid penetration and dry-heating pretreatment - Wen-Xuan Hu; Xin-Rui Hu; Fan Jiang; Yulian Zhu; Min Yang; Qin Dan; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2024)

Relationship of solid fuels use with cognitive function and efficacy of switching to cleaner fuels or using ventilation: A systematic review and meta-analysis - Rui Yang; Jie He; Kang-kang Zhong; Ming-xuan Fan; Teng Bao; Xue-Chun Liu; Qi Zhong (Environmental Research, 2024)

Effect of nano-SiO2 modification on the seismic performance of recycled aggregate concrete shear walls - Yingwu Zhou; Liu Fan; Feng Xing; Wenwei Lin; Rui Hu; Menghuan Guo; Zhongfeng Zhu (Engineering Structures, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Beneficial action of cinnamic acid against ovarian cancer via network pharmacology analysis and the pharmacological activity assessment - Rong Fan; Zining Liang; Qing Wang; Sizhe Chen; Shiting Huang; Jiansu Liu; Rui Huang; Jie Chen; Feilan Zhao; Wei Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

5G assisted GNSS precise point positioning ambiguity resolution - Fangxin Li; Rui Tu; Pengfei Zhang; Rui Zhang; Lihong Fan; Siyao Wang; Xiaochun Lu (Journal of Geodesy, 2024)

Integrated metabolomic and transcriptomic analyses provide comprehensive new insights into the mechanism of chitosan delay of kiwifruit postharvest ripening - Haiying Yang; Xueli Zhang; Rui Wu; Xiaoli Tang; Yanqing Yang; Xinguang Fan; Hansheng Gong; Donald Grierson; Xueren Yin; Jianzhao Li; Aidi Zhang (Postharvest Biology and Technology, 2024)

Improving prediction of soil heavy metal(loid) concentration by developing a combined Co-kriging and geographically and temporally weighted regression (GTWR) model - Huijuan Wang; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Boya Cai; Rui Tang; Jiaxun Sun; Zilin Han; Jing Yang; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2024)

Oxygen-enriched vacancy spinel Mn-Co oxides by deep thermal reduction for enhanced antibiotics degradation efficiency - Xiai Zhang; Rui Zhou; Ruohong Bi; Tong Wang; Qikui Fan; Hao Zhu; Zhimao Yang; Xiaofei Liu; Chuncai Kong (Journal of Environmental Chemical Engineering, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

Ternary Zn3V3O8 superstructure and synergistic modification of separator promote high performance and stable zinc ion battery - Rui Sun; Peng Xia; Xincheng Guo; Siyang Dong; Feng Xu; Yufei Zhang; Shengjun Lu; Qiang Zheng; Haosen Fan (Chemical Engineering Journal, 2024)

Water-assisted catalytic transfer hydrogenation of guaiacol to cyclohexanol over Ru/NiAl2O4 - Yuying Zhao; Jiahui Zhan; Rui Hu; Gang Luo; Jiajun Fan; James H. Clark; Shicheng Zhang (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

Analysis of genetic parameters of growth and wood traits provides insight into the genetic improvement of Schima superba - Yunpeng Wang; Guoliang Wu; Shaohua Huang; Lizhen Ma; Huihua Fan; Rui Zhang; Zhichun Zhou (Tree Genetics & Genomes, 2024)

Correction to: An integrated velocity model application in ST area, Dongying Depression, China - Qinghui Xie; Hongche Fan; Junhao Chen; Zhifeng Rui; Chuan Wu; Yanming Tong (Acta Geophysica, 2024)

Zinc and COVID-19: Immunity, Susceptibility, Severity and Intervention - Fan Wang; Jiayi Zhong; Rui Zhang; Yongzhi Sun; Yingran Dong; Maoqing Wang; Changhao Sun (Critical Reviews in Food Science and Nutrition, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Understanding phosphorus mobilization mechanisms in acidic soil amended with calcium-silicon-magnesium-potassium fertilizer - Jilin Lei; Junhui Yin; Shuo Chen; Owen Fenton; Rui Liu; Qing Chen; Bingqian Fan; Shuai Zhang (Science of The Total Environment, 2024)

Titanium carbide-based nanocomposite: A promising reinforcing material for enzymatic CO2 conversion - Menglei Mao; Ruqing Chong; Feixue Sun; Rui Gao; Zihui Meng; Xinlong Fan; Wenfang Liu (Journal of Cleaner Production, 2024)

Occurrence, transmission and risks assessment of pathogens in aquatic environments accessible to humans - Yiyi Su; Rui Gao; Fang Huang; Bin Liang; Jianhua Guo; Lu Fan; Aijie Wang; Shu-Hong Gao (Journal of Environmental Management, 2024)

Parasitoid fitness and quality of Corcyra cephalonica (Stainton) eggs after vacuum packaging combined with cold storage - Ye Zhang; Wenya Zhu; Wenhao Mei; Rui Fan; Juan Wang; Jianzhen Zhang (Journal of Asia-Pacific Entomology, 2024)

Boric acids decorated polymers with Au nanoparticle anchor assisted laser desorption/ionization for qualitive and quantitative analysis of hydroxytyrosol in red wines - Xiaohui Huang; Baichun Wang; Rui Zhai; Chuan-Fan Ding; Xiang Fang; Xinhua Dai; Yinghua Yan (Food Chemistry, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Impact of economic development on soil trace metal(loid)s pollution: A case study of China - Boya Cai; Rui Tang; Huijuan Wang; Jiaxun Sun; Menglu Zhao; Xinmiao Huang; Xiaoyong Song; Zilin Han; Zhengqiu Fan (Environmental Pollution, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Monocyclic aromatic hydrocarbons production from NaOH pretreatment metallized food plastic packaging waste through microwave pyrolysis coupled with ex-situ catalytic reforming - Letian Zhang; Qiuhao Wu; Liangliang Fan; Rui Liao; Jiahui Zhang; Rongge Zou; Krik Cobb; Roger Ruan; Yunpu Wang (Chemical Engineering Journal, 2024)

Covalent-Metal organic Frameworks: Preparation and applications - Zhaobo Wang; Chen Wang; Qiming Hu; Xuefei Lei; Rui Guo; Junhua You; Ye Tian; Fan Yang; Meili Lv (Chemical Engineering Journal, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Aerosol effects on the three-dimensional structure of organized precipitation systems over Beijing-Tianjin-Hebei region in summer - Jing Xi; Rui Li; Xiaoye Fan; Yu Wang (Atmospheric Research, 2024)

Effects of elevated CO2 and spinetoram on the population fitness and detoxification enzymes activities in Frankliniella occidentalis and F. intonsa - Zongfang Fan; Yaping Chen; Rui Fan; Bin Chen; Lei Qian; Furong Gui (Journal of Pest Science, 2024)

Data-Driven Approaches for Vibroacoustic Localization of Leaks in Water Distribution Networks - Rongsheng Liu; Salman Tariq; Ibrahim A. Tijani; Ali Fares; Beenish Bakhtawar; Harris Fan; Rui Zhang; Tarek Zayed (Environmental Processes, 2024)
This study aims to propose Micro-electromechanical System (MEMS) accelerometers for leak localization in the water distribution network and assess the performance of machine learning models in accurately estimating leak locations. Intensive field experimentation was conducted to collect data for model development. Machine learning algorithms were employed to develop leak localization models, specifically artificial neural network (ANN) and support vector machine (SVM). Seventeen time-domain and frequency-domain features were extracted, and feature selection was performed using the backward elimination method. The results indicate that the ANN and SVM models are suitable classifiers for localizing leak distance. Both models achieved leak location predictions with over 80% accuracy, and the mean absolute errors were measured at 0.858 and 0.95 for the ANN and SVM models, respectively. The validation results demonstrated that the models maintained accuracies close to 80% when the distance between sensors and the leak was less than 15 m. However, the performance of the model deteriorates when leaks occur at distances greater than 15 m. This study demonstrates the applicability of MEMS accelerometers for leak localization in water distribution networks. The findings highlight the promising potential of employing MEMS accelerometers-based ANN and SVM models for accurate leak localization in urban networks, even under real-world, uncontrolled conditions. However, the current model exhibits limited performance in long-distance leak localization, requiring further research to address and resolve this issue.

Drought-related wildfire accounts for one-third of the forest wildfires in subtropical China - Jianpeng Yin; Binbin He; Chunquan Fan; Rui Chen; Hongguo Zhang; Yiru Zhang (Agricultural and Forest Meteorology, 2024)

Occurrence characteristics and influencing factors of antibiotic resistance genes in rural groundwater in Henan Province - Kai Zhang; Kuangjia Li; Feiyue Hu; Rui Xin; Penglin Fan; Yarou Lu; Ningning Wang; Mengyuan Qin; Ruojing Li (Environmental Science and Pollution Research, 2024)

Probabilistic assessment of seismic earth pressure against backfills with a nonlinear failure criterion - Rui Zhang; Xiangqian Sheng; Wenliang Fan (Soil Dynamics and Earthquake Engineering, 2024)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

Impacts of climate change and human activity on the potential distribution of Aconitum leucostomum in China - Li Xu; Yuan Fan; Jianghua Zheng; Jingyun Guan; Jun Lin; Jianguo Wu; Liang Liu; Rui Wu; Yujia Liu (Science of The Total Environment, 2024)

Impacts of re-vegetation on soil water dynamics in a semiarid region of Northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li (Science of The Total Environment, 2024)

Satellite observed aboveground carbon dynamics in Africa during 2003–2021 - Mengjia Wang; Philippe Ciais; Rasmus Fensholt; Martin Brandt; Shengli Tao; Wei Li; Lei Fan; Frédéric Frappart; Rui Sun; Xiaojun Li; Xiangzhuo Liu; Huan Wang; et al. (Remote Sensing of Environment, 2024)

Epsilon-poly-l-lysine alleviates brown blotch disease of postharvest Agaricus bisporus mushrooms by directly inhibiting Pseudomonas tolaasii and inducing mushroom disease resistance - Rui Song; Xiuhong Wang; Lu Jiao; Hanyue Jiang; Shuai Yuan; Lei Zhang; Zixuan Shi; Zhenchuan Fan; Demei Meng (Pesticide Biochemistry and Physiology, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Agronomic performances of biodegradable and non-biodegradable plastic film mulching on a maize cropping system in the semi-arid Loess Plateau, China - Hao ZHANG; Mengqiong CHEN; Ruiquan QIAO; Fan DING; Hao FENG; Rui JIANG (Pedosphere, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Fe-MOFs/CuS nanocomposite-mediated peroxymonosulfate activation for tetracycline degradation: Boosted dual redox cycles - Rui Ma; Zhijie Chen; Weihang Xu; Ran Yu; Yichu Zhang; Fan Chen; Xiaoming Peng; Bing-Jie Ni; Jin Qian (Journal of Cleaner Production, 2024)

Estimation of potential wildfire behavior characteristics to assess wildfire danger in southwest China using deep learning schemes - Rui Chen; Binbin He; Yanxi Li; Chunquan Fan; Jianpeng Yin; Hongguo Zhang; Yiru Zhang (Journal of Environmental Management, 2024)

Evolution of carbon deposits during ethylene aromatization over Zn/ZSM-5 - Rui Geng; Yacong Liu; Yanxia Guo; Mei Dong; Sen Wang; Weibin Fan; Jianguo Wang; Zhangfeng Qin (Fuel, 2024)

The promotion effect of Pr doping on the catalytic performance of MnCeOx catalysts for low-temperature NH3-SCR - Tong Wu; Shan Ren; Rui-tang Guo; Chu-fan Li; Yi-hao You; Shi-yi Guo; Wei-guo Pan (Fuel, 2024)

Anti-inflammasome bio-heterojunction (AI-bioHJ): Revolutionizing diabetic wound healing with in situ self-transformation and programmed gas therapy - Fan Yang; Rui Shu; Bin Li; Wenyu Dai; Wanxi Chen; Jiamin Sun; Ding Bai; Weizhong Yang; Yi Deng (Chemical Engineering Journal, 2024)

Microbial response and spatial profiling of nitrite-producing denitrification granular sludge in-situ exposed to high nitrite stress - Jiarui Fan; Rui Du; Qingtao Liu; Cong Li; Yongzhen Peng (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Study on the Mechanism of Rock Damage Under Microwave and Laser Irradiation Through Multiscale and Multiphysics Numerical Modelling - Fuxin Rui; Gao-Feng Zhao; Yuliang Zhang; Lifeng Fan; Xiaobao Zhao (Rock Mechanics and Rock Engineering, 2024)

Responses of carbon and microbial community structure to soil nitrogen status vary between maize and potato residue decomposition - Linkang Chen; Ping Zhao; Chunyan Ming; Wenchun Yu; Rui Xiang; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2024)

Genetic Diversity and Population Structure of Chinese Longsnout Catfish (Leiocassis longirostris) Using Microsatellite DNA Markers - Yanling Hou; Huan Ye; Xinhua Song; Jiahui Fan; Junyi Li; Jian Shao; Yizhou Wang; Danqing Lin; Huamei Yue; Rui Ruan; Chuangju Li (Fishes, 2024)
The Chinese longsnout catfish (Leiocassis longirostris) is an economically important freshwater fish in China; however, its wild resources have declined dramatically in recent decades. Understanding the genetic structure of Chinese longsnout catfish populations is crucial to guide breeding programs and fishy restoration. In this study, 15 highly polymorphic microsatellite DNA loci were used to evaluate its genetic diversity and population structure. Chinese longsnout catfish populations show high genetic diversity; they do not show significant genetic differentiation or systematic geographic pattern of variation. From the upper to the lower reaches of the Yangtze River, the genetic diversity of Chinese longsnout catfish populations showed an increasing trend. The Gezhouba and Three Gorges dams, which physically divide the Yangtze River into upstream and mid-downstream sections, did not contribute to the genetic differentiation of Chinese longsnout catfish populations. Hence, the source of broodstock is not critical for within-river breeding programs and stock enhancement to restore the wild population. In addition, possible effects of dams on differentiation among populations are crucial and long-term evaluation is essential.

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Petrogenesis and tectonic implication of the Triassic syenitic complexes in the eastern Qinling orogen, central China - Zhen-Yu Wang; Hong-Rui Fan; Hai-Dong She; Kui-Feng Yang (Journal of Asian Earth Sciences, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Expansive microbial metabolic versatility and spatial biodiversity of anammox coupling with denitrification granular sludge under different feeding strategies - Cong Li; Rui Du; Qingtao Liu; Jiarui Fan; Yongzhen Peng (Chemical Engineering Journal, 2024)

Novel insights into mass transfer-controlled radical-mediated co-pyrolysis of lignin with typical plastics - Yuyang Fan; Chao Liu; Zhengxue Zhang; Jia Ouyang; Fuli Deng; Ruixue Zhao; Huiyan Zhang; Rui Xiao (Chemical Engineering Journal, 2024)

Regulation of oxygen vacancy concentration over ZnCr oxide in bifunctional catalyst for the direct conversion of syngas to light olefins - Daoming Jin; Zhong Xin; Xin Meng; Wenhua Dai; Bowen Xu; Rui Zhao; Fan Xu; Dandan Yang (Chemical Engineering Journal, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

One pot synthesis of hydrophobic nanochitin aerogel via tert-butyl alcohol/water binary solvents as antibacterial and renewable oil superabsorbent - Liang Liu; Xinxia Li; Rui Zhou; Yimin Fan (Carbohydrate Polymers, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Human activities contributing to the accumulation of high-risk trace metal(loid)s in soils of China's five major urban agglomerations - Rui Tang; Boya Cai; Huijuan Wang; Xinmiao Huang; Xiaoyong Song; Zilin Han; Menglu Zhao; Jiaxun Sun; Honghui Huang; Jian Huang; Zhengqiu Fan (Science of The Total Environment, 2023)

Hydroxyapatite (HAP) formation in acetate-driven partial denitrification process: Enhancing sludge granulation and phosphorus removal - Yu Lan; Xing Li; Rui Du; Xiaoyan Fan; Shenbin Cao; Yongzhen Peng (Science of The Total Environment, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Neuroprotective α-pyrones from Nigrospora oryzae, an endophytic fungus residing in Taxus chinensis var. mairei - Zi Yun Fan; Jing Peng; Jun Qiao Lou; Yong Chen; Xue Ming Wu; Rui Tan; Ren Xiang Tan (Phytochemistry, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Microalgae biofilm photobioreactor and its combined process for long-term stable treatment of high-saline wastewater achieved high pollutant removal efficiency - Gaozhong Fan; Jie Huang; Xin Jiang; Weile Meng; Rui Yang; Jinsong Guo; Fang Fang; Jixiang Yang (Journal of Environmental Chemical Engineering, 2023)

CeO2 nanorods with bifunctional oxygen vacancies for promoting low-pressure photothermocatalytic CO2 conversion with CH3OH to dimethyl carbonate - Shanbiao Jin; Xiushuai Guan; Xiaochao Zhang; Changming Zhang; Jianxin Liu; Yawen Wang; Yunfang Wang; Rui Li; Zhong Li; Caimei Fan (Journal of Environmental Chemical Engineering, 2023)

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

Recent advances in stability improvement of anthocyanins by efficient methods and its application in food intelligent packaging: A review - Rui Tang; Yong He; Kai Fan (Food Bioscience, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Improvement of Soil Structure and Bacterial Composition by Long-Term Application of Seaweed Fertilizer - Liu Qiqin; Zhou Huaguang; Sun Minxiu; Li Qian; Fan Haijun; Chen Haimin; Yang Rui (Journal of Soil Science and Plant Nutrition, 2023)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Application of high-throughput sequencing technologies and analytical tools for pathogen detection in urban water systems: Progress and future perspectives - Yanmei Zhao; Fang Huang; Wenxiu Wang; Rui Gao; Lu Fan; Aijie Wang; Shu-Hong Gao (Science of The Total Environment, 2023)

4-Phenylbutyric acid may prevent mouse ovarian and uterine damage due to procymidone-induced alteration of circRNA Scar and circZc3h4 levels by controlling excessive unfolded protein response - Rui Li; Fan Li; Xuning Wang; Mingxin Bai; Hu Fu; Zhengli Yan; Xiaoping Yang; Yongfei Zhu (Pesticide Biochemistry and Physiology, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Pyrolysis of different types of waste cooking oil in the presence/absence HZSM-5 catalyst: Influence of feedstock characteristics on aromatic formation - Yuanyuan Wang; Yuan Zeng; Liangliang Fan; Qiuhao Wu; Letian Zhang; Jianyun Xiong; Jiahui Zhang; Rui Liao; Kirk Cobb; Yuhuan Liu; Roger Ruan; Yunpu Wang (Fuel, 2023)

Highly dispersed Fe/EG catalysts assisted by ammonium citrate and their application in CO2 hydrogenation to olefins - Rui Zhao; Xin Meng; Wenhua Dai; Daoming Jin; Bowen Xu; Fan Xu; Dandan Yang; Zhong Xin (Fuel, 2023)

Insights into brain perceptions of the different taste qualities and hedonic valence of food via scalp electroencephalogram - Tianyi Yang; Peng Zhang; Lidong Xing; Jin Hu; Rui Feng; Junjie Zhong; Weitao Li; Yizhi Zhang; Qiaoqiao Zhu; Yamin Yang; Fan Gao; Zhiyu Qian (Food Research International, 2023)

Injection of l-arginine or l-lysine before freezing delays the emulsifying and gelling properties deterioration of myofibrillar proteins of frozen porcine Longissimus lumborum muscle - Rui Li; Xiaokang Fan; Xun Gao; Cunliu Zhou (Food Chemistry, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Occurrences of typical PPCPs during wastewater treatment and the composting of sewage sludge with micron-sized and nano-sized Fe3O4 - Jishao Jiang; Rui Hou; Huilin Cui; Dong Liu; Guangxuan Yan; Yujuan Fan; Ke Cheng; Zhiguo Cao (Environmental Pollution, 2023)

ZIF-derived Fe,Co coordinated N/O-codoped three-dimensional tungsten–carbon matrix for the performance-enhanced zinc-air flow battery and water splitting - Jinling Xue; Zhipeng Liu; Yibin Fan; Rui Wang; Yinshi Li (Chemical Engineering Journal, 2023)

Geological resources of scandium: a review from a Chinese perspective - Shang Liu; Hong-Rui Fan; M. Santosh; Xuan Liu; Qi-Wei Wang; Alan R. Butcher (International Geology Review, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Hydrogeological controls on chromium enrichment along the groundwater flow path in the Baiyangdian Catchment, North China Plain - Chao Liu; Huaming Guo; Wendi Fan; Rui Xu; Shuangbao Han; Bingying Gao; Bo Zhao; Chunping Jiang (Science of The Total Environment, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Triazole fungicides exert neural differentiation alteration through H3K27me3 modifications: In vitro and in silico study - Tingting Ku; Xin Tan; Yutong Liu; Rui Wang; Lifan Fan; Zhihua Ren; Xia Ning; Guangke Li; Nan Sang (Journal of Hazardous Materials, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

Simultaneous nitrite production and phosphorus removal by partial denitrification-hydroxyapatite (PD-HAP) coupled process from high-nitrate wastewater - Yu Lan; Rui Du; Xiaoyan Fan; Shenbin Cao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

New insights into health risk assessment on soil trace metal(loid)s: Model improvement and parameter optimization - Jiaxun Sun; Xinmiao Huang; Xiaoyong Song; Rui Tang; Menglu Zhao; Boya Cai; Huijuan Wang; Zilin Han; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2023)

Trade-off strategy for the usage of thiencarbazone-methyl·isoxaflutole on maize fields: Nitrogen-associated microbial response and environmental implications - Yonglu Wang; Fengsong Zhang; Lida Wang; Huajun Fang; Guixiang Zhang; Xiumei Zhao; Siyi Liu; Qingchao Li; Yue Liu; Rui Ren; Yu An; Lisha Fan (Journal of Cleaner Production, 2023)

Experimental study on microstructural modification of coal by liquid CO2 extraction - Hu Wang; Hu Wen; Zhenbao Li; Rui Liang; Fengshuang Wang; Shixing Fan; Rijun Li (Fuel, 2023)

Design and operation investigation for the fifth-generation heating and cooling system based on load forecasting in business districts - Ting Bu; Rui Fan; Bin Zheng; Kexin Sun; Yibing Zhou (Energy and Buildings, 2023)

SymmetricNet: end-to-end mesoscale eddy detection with multi-modal data fusion - Yuxiao Zhao; Zhenlin Fan; Haitao Li; Rui Zhang; Wei Xiang; Shengke Wang; Guoqiang Zhong (Frontiers in Marine Science, 2023)
Mesoscale eddies play a significant role in marine energy and matter transportation. Due to their huge impact on the ocean, mesoscale eddy detection has been studied for many years. However, existing methods mainly use single-modal data, such as the sea surface height (SSH), to detect mesoscale eddies, resulting in inaccurate detection results. In this paper, we propose an end-to-end mesoscale eddy detection method based upon multi-modal data fusion. Particularly, we don’t only use SSH, but also add data of other two modals, i.e., the sea surface temperature (SST) and the velocity of flow, which are closely related to mesoscale eddy detection. Moreover, we design a novel network named SymmetricNet, which is able to achieve multi-modal data fusion in mesoscale eddy detection. The proposed SymmetricNet mainly contains a downsampling pathway and an upsampling pathway, where the low-level feature maps from the downsampling pathway and the high-level feature maps from the upsampling pathway are merged through lateral connections. In addition, we apply dilated convolutions to the network structure to increase the receptive field without sacrificing resolution. Experiments on multi-modal mesoscale eddy dataset demonstrate the advantages of the proposed method over previous approaches for mesoscale eddy detection.

Recent advances in core-shell structured catalysts for low-temperature NH3-SCR of NOx - Tong Wu; Rui-tang Guo; Chu-fan Li; Yi-hao You; Wei-guo Pan (Chemosphere, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Can China achieve its 2030 and 2060 CO2 commitments? Scenario analysis based on the integration of LEAP model with LMDI decomposition - Yimin Huang; Yuan Wang; Jiaoting Peng; Fan Li; Lin Zhu; Huihui Zhao; Rui Shi (Science of The Total Environment, 2023)

Evaluation of sludge anaerobic fermentation driving partial denitrification capability: In view of kinetics and metagenomic mechanisms - Qingtao Liu; Cong Li; Jiarui Fan; Yongzhen Peng; Rui Du (Science of The Total Environment, 2023)

First occurrence of caryocaridids (Crustacea, Phyllocarida) in the Ordovician of North China - Yi-long Liu; Ruo-ying Fan; Rui-wen Zong; Yi-ming Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Prediction of Permian karst reservoirs in the Yuanba gas field, northern Sichuan Basin, China - Yuxin Hao; Rebecca Bell; Ying Rao; Rui Fan; Yanghua Wang (Marine and Petroleum Geology, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Semantic segmentation of urban building surface materials using multi-scale contextual attention network - Fan Xu; Man Sing Wong; Rui Zhu; Joon Heo; Guoqiang Shi (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of different concentrations of gellan gum with/without 0.50% basil essential oil on the physicochemical properties of gellan gum-rice bran oil coating emulsions and their application in egg preservation - Dongmei Pan; Yakai Li; Yue Hu; Rui Li; Xun Gao; Xiaokang Fan; Hongmei Fang; Qiang Du; Cunliu Zhou (Food Chemistry, 2023)

Preparation of bio-jet fuels by a controllable integration process: Coupling of biomass fermentation and olefin polymerization - Yuehui Luo; Rui Zhang; Yuting He; DanFeng Lou; Rui Zhu; Can Zhu; Minghui Fan; Quanxin Li (Bioresource Technology, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Fish Swimming Traces from the Upper Devonian of Wuhan, South China - Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Journal of Earth Science, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Inactivation of Alicyclobacillus contaminans spores by dielectric barrier discharge plasma and its biological mechanism - Zewei Wang; Qiannan Zhao; Yuan Gan; Qiuxia Fan; Zhongqiu Hu; Zhouli Wang; Rui Cai; Tianli Yue; Yahong Yuan (Innovative Food Science & Emerging Technologies, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Eastward extension of the Solonker Suture beneath the central Songliao Basin, NE China: Evidence from a deep seismic reflection profile - Ming-Rui Li; Rui Gao; Jian-Bo Zhou; Simon A Wilde; He-Sheng Hou; Xiao-Fan Deng (Gondwana Research, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Multifunctional SiC aerogel reinforced with nanofibers and nanowires for high-efficiency electromagnetic wave absorption - Limeng Song; Chengwen Wu; Qing Zhi; Fan Zhang; Bozhen Song; Li Guan; Yongqiang Chen; Hailong Wang; Rui Zhang; Bingbing Fan (Chemical Engineering Journal, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Facet-Controlled Cu-doped and K-promoted Fe2O3 nanosheets for efficient CO2 hydrogenation to liquid hydrocarbons - Chuan Qin; Yixiong Du; Ke Wu; Yanfei Xu; Rui Li; Haifeng Fan; Di Xu; Mingyue Ding (Chemical Engineering Journal, 2023)

Late Pleistocene zinc isotopic indices of paleoproductivity variations in the tropical West Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Liang Du; Yipeng Wang; Yujin Fan; Rui Zhang; Tiegang Li; James Russell; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; et al. (CATENA, 2023)

Transcriptional analysis of the dimorphic fungus Umbilicaria muehlenbergii reveals the molecular mechanism of phenotypic transition - Dongjie Fan; Lushan Liu; Shunan Cao; Rui Liao; Chuanpeng Liu; Qiming Zhou (World Journal of Microbiology and Biotechnology, 2023)

Effect of exogenous Ca on the physiology and growth indicators of pakchoi under foliar and root fluorine stress - Rui Liu; Si-fan Cui; Chun-dan Gan; Jin-yan Yang (Environmental Geochemistry and Health, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Emerging poly- and perfluoroalkyl substances in water and sediment from Qiantang River-Hangzhou Bay - Haixiang Cheng; Hangbiao Jin; Bin Lu; Chenhan Lv; Yinghui Ji; Hui Zhang; Rui Fan; Nan Zhao (Science of The Total Environment, 2023)

Zn, O Co-adsorption based on MOF-5 for efficient capture of radioactive iodine - Rui-Li Yu; Qian-Fan Li; Tong Zhang; Zhen-Le Li; Liang-Zhi Xia (Process Safety and Environmental Protection, 2023)

Developing effective radio frequency and ultraviolet combination technology based on evaluating quality characteristics of buckwheat - Juanjuan Xu; Liumin Fan; Dingting Zhou; Gaoji Yang; Xiangyu Guan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Developing radio frequency pretreatment technology for improving yield and quality of flaxseed oil extractions - Liumin Fan; Juanjuan Xu; Xiangyu Guan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Gold endowment and unloading along pathway for giant gold mineralization: Insights from spatiotemporal variations of in-situ pyrite geochemistry and gold fineness from the Jiaodong gold deposits, north China Craton - Ting-Guang Lan; Hong Wang; Hong-Rui Fan; Thomas Ulrich; Huan-Long Hu; You-Wei Chen; Lei Shu (Gondwana Research, 2023)

Quantitative analysis of rainwater redistribution and soil loss at the surface and belowground on karst slopes at the microplot scale - Chunhua Fan; Longshan Zhao; Rui Hou; Qian Fang; Jinxin Zhang (CATENA, 2023)

Production of antifungal iturins from vegetable straw: A combined chemical-bacterial process - Yuan Yuan; Depeng Chu; Jiajun Fan; Zhenzhen Cui; Rui Wang; Han Zhang; Xiangwei You; Yiqiang Li; Xiaoqiang Wang (Bioresource Technology, 2023)

Spatial Equity of Basic Education Resources and Coordinated Regional Development in Xinjiang, China - Tao Han; Jie Fan; Rui Guo; Yong Sun; Dong Chen; Baoying Liu; Yanan Lian (Chinese Geographical Science, 2023)

An elevation mask modeling method based on azimuth rounding for monitoring building deformation - Han Junqiang; Tu Rui; Lu Xiaochun; Xiao Xia; Zhang Rui; Fan Lihong; Zhang Pengfei; Wang Siyao (Acta Geodaetica et Geophysica, 2023)

Seismic imaging of the Java subduction zone: New insight into arc volcanism and seismogenesis - Fan Xie; Zewei Wang; Dapeng Zhao; Rui Gao; Xiaofei Chen (Tectonophysics, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

High-resolution records of sea surface temperature and salinity in the East China Sea over the past 14.2 kyr: Implication from alkenone and its hydrogen isotopes - Rui Zhang; Wenlong Pei; Yipeng Wang; Xinling Wang; Jiayue Wang; Tiegang Li; James Russell; Fan Zhang; Zhiyong Liu; Minglei Guan; Qi Han; Chenyang Tian; et al. (Global and Planetary Change, 2023)

A dispersive solid-phase extraction method for the determination of Aristolochic acids in Houttuynia cordata based on MIL-101(Fe): An analytes-oriented adsorbent selection design - Rui Cheng; Xuejin Mao; Jiaying Yu; Fan Liu; Lan Guo; Dongmei Luo; Yiqun Wan (Food Chemistry, 2023)

Cognitive outcomes caused by low-level lead, cadmium, and mercury mixture exposure at distinct phases of brain development - Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Yanhui Zhu; Guihua Du; Jie Xie; Fankun Zhou; Chang Feng; Guangqin Fan (Food and Chemical Toxicology, 2023)

A sulfonate-functionalized covalent organic framework for record-high adsorption and effective separation of organic dyes - Rui Li; Xihao Tang; Jialin Wu; Kai Zhang; Qianni Zhang; Jiaqi Wang; Jiayue Zheng; Shengrun Zheng; Jun Fan; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2023)

Diversity of Fusarium community assembly shapes mycotoxin accumulation of diseased wheat heads - Qiang Wang; Rui Song; Sanhong Fan; Jeffrey J. Coleman; Xiangming Xu; Xiaoping Hu (Molecular Ecology, 2023)
Fusarium head blight (FHB) is a major disease worldwide on cultivated cereals, caused by several Fusarium species. FHB can cause not only yield reduction but also accumulation of mycotoxins in the grain contaminating the food supply. Much of the earlier research has focused on Fusarium pathogenesis, conditions required for disease development and toxin accumulation, and FHB management. However, the Fusarium community composition within the micro‐habitat of a single diseased wheat head in the field has had limited investigation. Similarly, the relationship between the Fusarium community structure and mycotoxin accumulation within diseased heads remains unclear. In the present study, we investigated the Fusarium community in diseased heads sampled from different geographical sites in China. Several sites in Shandong province formed a transitional region which contained highly variable profiles of Fusarium OTUs, where a single diseased head could contain more than 10 Fusarium OTUs. Mycotoxin accumulation was independent of geographical properties, however, deoxynivalenol, 15‐acetyldeoxynivalenol and zearalenone concentrations showed a significant negative correlation with Fusarium diversity on diseased heads while a significant positive correlation between nivalenol concentration and Fusarium diversity was observed. Taken together, the Fusarium OTU diversity within diseased heads in the field significantly influences mycotoxin accumulation, providing an important point to consider in FHB disease management and mycotoxin research.

An integrated velocity model application in ST area, Dongying Depression, China - Qinghui Xie; Hongche Fan; Junhao Chen; Zhifeng Rui; Chuan Wu; Yanming Tong (Acta Geophysica, 2023)

The mechanism of gibberellins treatment suppressing kiwifruit postharvest ripening processes by transcriptome analysis - Haiying Yang; Jianzhao Li; Xiaohe Li; Rui Wu; Xueli Zhang; Xinguang Fan; Guotian Li; Hansheng Gong; Xueren Yin; Aidi Zhang (Postharvest Biology and Technology, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Litchi-like glucose oxidase-integrated magnetic metal-organic framework as glucose-triggered cascade catalyst for antibacterial treatment - Hang Jia; Shiqi Fan; Rui Cai; Zhouli Wang; Yahong Yuan; Tianli Yue (Journal of Environmental Chemical Engineering, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

MIL-101(Cr)@Fe3O4 nanocomposites as magnetic solid-phase extraction adsorbent for the determination of multiple mycotoxins in agricultural products by ultra-high-performance liquid chromatography tandem mass spectrometry - Dakai Guo; Qingwen Huang; Rui Zhao; Wenbo Guo; Kai Fan; Zheng Han; Zhihui Zhao; Dongxia Nie (Food Control, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Hysteretic performance of self-centering buckling-restrained braces with embedded friction spring - Lei Chen; Dongsheng Wang; Fan Shi; Rui Zhang; Zhiguo Sun (Engineering Structures, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

Trophoblast-specific knockdown of CSPG4 expression causes pregnancy complications with poor placentation in mice - Junfei Xu; Anwen Yuan; Rui Su; Qing Yang; Xiujun Fan; Juzuo Zhang (Reproductive Biology, 2023)

Spatio-temporal characteristics of soil Cd pollution and its influencing factors: A Geographically and temporally weighted regression (GTWR) method - Menglu Zhao; Huijuan Wang; Jiaxun Sun; Rui Tang; Boya Cai; Xiaoyong Song; Xinmiao Huang; Jian Huang; Zhengqiu Fan (Journal of Hazardous Materials, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Biomimetic chitosan nanoparticles with simultaneous water lubricant and anti-inflammatory - Lumin Yang; Haofei Huang; Huajing Zeng; Xiaoduo Zhao; Rui Wang; Zhengfeng Ma; Zengjie Fan; Yong-min Liang; Shuanhong Ma; Feng Zhou (Carbohydrate Polymers, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Orbit determination of BeiDou navigation satellite system maneuvered satellites based on instantaneous velocity pulses parameters - Rui Zhang; Rui Tu; Junqiang Han; Pengfei Zhang; Lihong Fan; Siyao Wang; Xiaochun Lu (Advances in Space Research, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Marine osmium‑uranium‑sulfur isotope evidence for the interaction of volcanism and ocean anoxia during the Middle Pleistocene in the tropical Western Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Rui Zhang; Tiegang Li; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; Minglei Guan; Qi Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

WITHDRAWN:Prediction of Permian karst reservoirs in the Yuanba gas field, northern Sichuan Basin, China - Yuxin Hao; Rebecca Bell; Dongfeng Hu; Rui Fan; Yanghua Wang (Marine and Petroleum Geology, 2023)

Recent progress of CeO2-based catalysts with special morphologies applied in air pollutants abatement: A review - Tong Wu; Rui-tang Guo; Chu-fan Li; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2023)

Fire-resistant MXene composite aerogels for effective oil/water separation - Guixin Wang; Yuxin Xu; Rui Zhang; Shuang Gai; Ying Zhao; Fan Yang; Kui Cheng (Journal of Environmental Chemical Engineering, 2023)

Numerical investigation of a 1MW full-loop chemical looping combustion unit with dual CFB reactors - Liyan Sun; Rui Xiao; Junjie Lin; Dali Kong; Kun Luo; Jianren Fan (International Journal of Greenhouse Gas Control, 2023)

Metagenomics-based interpretation of selective bioaugmentation promoting partial-denitrification coupling with anammox process reactivation in suspended sludge system - Cong Li; Qingtao Liu; Jiarui Fan; Yongzhen Peng; Rui Du (Chemical Engineering Journal, 2023)

Inhibition of ice recrystallization by tamarind (Tamarindus indica L.) seed polysaccharide and molecular weight effects - Xianbao Sun; Rui Guo; Yuxing Kou; Hong Song; Taijie Zhan; Jinhong Wu; Lihua Song; Hui Zhang; Fan Xie; Jiangmei Wang; Zibo Song; Yan Wu (Carbohydrate Polymers, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Effects of dietary methionine on growth and body composition, indicators of digestion, protein metabolism and immunity, and resistance to heat stress of abalone Haliotis discus hannai - Hao Chen; Wenhao Fan; Hongyang Zhang; Panpan Yue; Rui Wang; Wenbing Zhang; Kangsen Mai (Aquaculture, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

In-situ cracking of oil into gas in reservoirs identified by fluid inclusion analysis: Theoretical model and case study - Yifan Song; Yong Chen; Miao Wang; Matthew Steele-MacInnis; Rui Ni; Hui Zhang; Junjia Fan; Xingzhi Ma; Zhenzhu Zhou (Marine and Petroleum Geology, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

Mobilization of water affecting formation and dissociation of hydrate in clay sediment - Peng Zhang; Xueping Chen; Lianhai Zhang; Shuaijun Li; Wenting Chen; Qingbai Wu; Shuanshi Fan; Rui Bao; Cuicui Mu (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Ulva prolifera polysaccharide enhances the root colonisation by Bacillus amyloliquefaciens strain Cas02 - Depeng Chu; Xiaoqiang Wang; Jiajun Fan; Lijuan Peng; Jinchang Liang; Yanfen Zheng; Rui Wang; Xiangwei You; Changliang Jing; James Clark; Yiqiang Li; Yuan Yuan (Carbohydrate Polymers, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Correction to: Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

Effect of herbaceous plants on the response of loose silty sand slope under rainfall - Pei Tai; Fan Wu; Rui Chen; Jingqi Zhu; Xiong Wang; Min Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Development of a matrix-based candidate reference material for human glycated albumin using isotope-dilution liquid chromatography/tandem mass spectrometry - Rui Zhang; Rui Zhao; Wenhua Ren; Mo Wang; Gaowei Fan; Jie Shi; Yichuan Song; Xiaojie Zhou; Qingtao Wang (Analytica Chimica Acta, 2023)

The influence of weather and temperature on pedestrian walking characteristics on the zigzag bridge - Fan Dong; Xiaolian Li; Qimiao Xie; Rui Ye; Shuchao Cao (International Journal of Biometeorology, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

Genome-wide identification of black pepper (Piper nigrum L.) Dof gene family and the differential gene screening in resistance to Phytophthora capsici - Fenju Zhang; Rui Fan; Lin Yan; Lisong Hu; Fan Su; Dewei Yang; Jing Li (Biologia, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Ri Jin Jiang; Fan Yang; Feng Chen; Rui Yin; Ming Zhi Liu; Wen Bin Zhu; Ai Guo; Lian Wei Liu (Frontiers in Marine Science, 2022)
Trophic research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 103 bigeye tuna ( Thunnus obesus ), 296 yellowfin tuna ( Thunnus albacores ), and 264 albacore tuna ( Thunnus alalunga ) samples were collected from September to December 2019. Samples for stomach content and stable isotope analysis were randomly selected. The stomach content analysis results showed that the stomach contents of the three tuna species were rich in prey, and 48 prey species were identified, including fish, cephalopods, and crustaceans, with high between-phenotype component (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity of bigeye tuna were higher than that of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate (35.69%) and lowest average stomach fullness index (0.064). The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant ( P <0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. Bigeye tuna mainly feed on Ommastrephes bartrami and Myctophidae, yellowfin tuna mainly feed on Hyperiidea and Aluterus monoceros , and albacore tuna mainly feed on Gempylus serpens and Loligo chinensis . The stable isotope results showed that the δ 13 C and δ 15 N values of the three tuna species were significant ( P <0.001). The standard ellipse area corrected for small sample sizes (SEAc) and total niche area (TA) of bigeye tuna, range of δ 15 N (NR) of yellowfin tuna, and range of δ 13 C (CR) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.

Oyster and Barnacle Recruitment Dynamics on and Near a Natural Reef in China: Implications for Oyster Reef Restoration - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Rui-Liang Fan; Wen-Kao Zhang; Wei-Min Quan (Frontiers in Marine Science, 2022)
Oysters and barnacles are dominant inhabitants of natural and restored oyster reefs around the world, and high areal coverage of barnacles at natural or restored reefs commonly decreases substrate accessibility for oyster settlement. The overall understanding of oyster and barnacle recruitment dynamics provides invaluable information on site selection and strategies employed for oyster reef restoration. This study documented the temporal and spatial patterns of oyster and barnacle recruitment on and near the largest natural intertidal oyster reef (Liyashan) in China during 2019–2020. The oyster Crassostrea sikamea recruitment appeared as a continuous process from June through late November or early December, with the peak in August. Greater recruits of oyster spat occurred on the sheltered inshore at the upstream of the natural oyster reef than on the reef and the nearby open coast ( p < 0.05). The barnacle recruitment extended from spring to early winter, with mid-spring and mid-summer peaks. Conversely, higher barnacle recruitment appeared on the natural oyster reef and the nearby open coast than on the sheltered inshore. Across all the monitoring sites, the cumulative recruits of oysters in each of 2019 and 2020 was negatively correlated with those of barnacles ( p < 0.05). The inshore sites (SH1 and SH2) with high oyster recruitment and low barnacle recruitment should be recognized as the natural spatfall sites for the natural oyster reef restoration. The separation in the recruitment peak between the oyster and the barnacle indicated that August was the most favorable window for capturing oyster spat through substratum addition to the water around the natural reef.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

The functional evolution and system equilibrium of urban and rural territories - Jie Fan; Sisi Li; Zhongrui Sun; Rui Guo; Kan Zhou; Dong Chen; Jianxiong Wu (Journal of Geographical Sciences, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Molecular Characterization and Expression Analysis of Glutaredoxin 5 in Black Tiger Shrimp (Penaeus monodon) and Correlation Analysis Between the SNPs of PmGrx5 and Ammonia-N Stress Tolerance Trait - Rui Fan; Shigui Jiang; Yundong Li; Qibin Yang; Song Jiang; Jianhua Huang; Lishi Yang; Xu Chen; Falin Zhou (Frontiers in Marine Science, 2022)
Glutaredoxins (Grxs) are glutathione-dependent oxidoreductases that belong to the thioredoxin (Trx) superfamily and are an essential part of the redox system in living organisms. However, there is a serious lack of sequence information and functional validation associated with Grxs in crustaceans. In this study, a new Grx gene ( PmGrx5 ) was identified and characterized in black tiger shrimp ( Penaeus monodon ). The full-length cDNA of PmGrx5 is 787 bp and consists of 114 bp 5′-UTR, 232 bp 3′-UTR, and 441 bp ORF, encoding a hypothetical protein of 146 amino acids. The putative PmGrx5 protein is 16.27 kDa with a theoretical isoelectric point of 5.90. Sequence alignment showed that PmGrx5 had the highest amino acid sequence homology with Grx5 from Penaeus vannamei at 98.63% and clustered with Grx5 from other crustaceans. Quantitative real-time PCR (qRT-PCR) analysis showed that PmGrx5 was expressed in all tissues examined, with a higher expression in the testis, stomach, lymphoid organ, and gill. PmGrx5 was continuously expressed during development, with the highest expression in zoea I. Ammonia-N stress and bacterial infection both differentially upregulated PmGrx5 expression in the hepatopancreas and gill. In addition, when PmGrx5 was inhibited, the expression of some other antioxidant enzymes was upregulated at the beginning of ammonia-N stress, but as the stress time increased, the expression of antioxidant enzymes was inhibited, the expression of apoptotic genes was increased, and the GSH content was significantly reduced. Inhibition of PmGrx5 led to a greater risk of oxidative damage in shrimp. In addition, the relationship between SNPs in exons of the PmGrx5 gene and tolerance to ammonia-N stress was identified and analysed. A total of nine SNPs were successfully identified, eight of which were significantly associated with ammonia and nitrogen stress tolerance trait in shrimp ( P < 0.05). The present study shows that PmGrx5 is involved in redox regulation and plays an important role in shrimp resistance to marine environmental stresses. Meanwhile, this study will provide a basis for molecular marker breeding in shrimp.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Yield responses of four common potato cultivars to an industry standard and alternative rotation in Atlantic Canada - Mohammad Amir Azimi; Yefang Jiang; Fan-Rui Meng; Kang Liang (American Journal of Potato Research, 2022)
This study was conducted to evaluate yield responses of four potato ( Solanum tuberosum L.) cultivars (‘Russet Burbank’, ‘Shepody’, ‘Gold Rush’, and ‘Russet Prospect’) and soil N dynamic changes to two 3-year rotations in Prince Edward Island, Canada. The two rotations were the local industry standard potato–barley ( Hordeum vulgare L. )–red clover ( Trifolium pratense L.) rotation (PBC) and an alternative potato–soybean ( Glycine max L.)–barley rotation (PSB). All potato cultivars received 170 kg N ha − 1 input at planting without irrigation. Soil mineral N content before potato planting was significantly higher under the PBC rotation. However, the PBC rotation produced significantly lower yields, suggesting the possibility of excessive N supply from the plowed-down red clover. While cultivar and the interaction between cultivar and rotation did not show a significant difference in yield, yields of all cultivars were positively affected by the PSB rotation. The Gold Rush cultivar was affected the most (36%), followed by Russet Burbank (17%) and Prospect (14%) cultivars, with Shepody being the least affected (3%) by the alternative PSB rotation. Russet Burbank was the highest yielding cultivar under both rotations. With the three russet cultivars combined as a single russet cultivar, the PSB rotation significantly increased tuber yields, while the Shepody cultivar did not significantly benefit from the PSB rotation, suggesting that the russet cultivars responded more sensitively to the alternative rotation. Results demonstrate that adequately accounting for N supply from a preceding green manure crop is required for sustainable potato production in this humid temperate region.

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Neuregulin-1 regulates the conversion of M1/M2 microglia phenotype via ErbB4-dependent inhibition of the NF-κB pathway - Yuqi Ma; Peixia Fan; Rui Zhao; Yinghua Zhang; Xianwei Wang; Weigang Cui (Molecular Biology Reports, 2022)

Association between glucagon-like peptide-1 receptor gene polymorphism and treatment response to GLP1R agonists in Chinese patients with type 2 diabetes: a prospective cohort study - Ziwan Guan; Yue Du; Rui Li; Shufang Zhang; Yuedong Xu; Xiaoqian Zhang; Fan Zhang; Ying Yin; Kunrong Wu; Xiaoli Li; Yan Li (European Journal of Clinical Pharmacology, 2022)

Physiological homeostasis alteration and cellular structure damage of Chlorella vulgaris exposed to silver nanoparticles with various microstructural morphologies - Ningcan Deng; Haibo Li; Yinghua Li; Fan Mo; Mingshuai Wang; Zhe Li; Xi Chen; Jianing Xu; Rui Chai; Hongxuan Wang (Environmental Science and Pollution Research, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

Gisenoside Rg1 attenuates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation - Teng-Teng Ren; Jia-Ying Yang; Jun Wang; Sheng-Rui Fan; Rongfeng Lan; Xiao-Yan Qin (Inflammation Research, 2021)

cDNA cloning and expression analysis of glutaredoxin 3 in black tiger shrimp Penaeus monodon - Rui Fan; Yundong Li; Shigui Jiang; Song Jiang; Qibin Yang; Lishi Yang; Jianhua Huang; Falin Zhou (Aquaculture International, 2021)

Slope system stability reliability analysis with multi-parameters using generalized probability density evolution method - Dezhi Zai; Rui Pang; Bin Xu; Qunying Fan; Mingyuan Jing (Bulletin of Engineering Geology and the Environment, 2021)

Sustained growth of the largest uninhabited alluvial island in the Changjiang Estuary under the drastic reduction of river discharged sediment - Xiaodong Zhang; Rui Xie; Daidu Fan; Zuosheng Yang; Hongmin Wang; Chuang Wu; Yuhan Yao (Science China Earth Sciences, 2021)

A novel amorphous solid dispersion based on drug–polymer complexation - Fan Meng; Rui Ferreira; Yongchao Su; Feng Zhang (Drug Delivery and Translational Research, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Light and high-strength structure inspired by the characteristics of double-nutrient foramens in intertarsal joint of ostrich - Rui Zhang; Chengjin Wang; Shichao Fan; Dong Li; Hao Pang; Lei Ling; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Regulation of Rothmund–Thomson syndrome protein RecQL4 functions in DNA replication by SIRT1-mediated deacetylation - Yuxia Yang; Wei Fan; Rong Wang; Rui Wang; Wei Gu; Jianyuan Luo (Genome Instability & Disease, 2021)

Well logging curve reconstruction based on kernel ridge regression - Pengpeng Fan; Rui Deng; Jinquan Qiu; Zhongliang Zhao; Shengli Wu (Arabian Journal of Geosciences, 2021)

Improving rice eating and cooking quality by coordinated expression of the major starch synthesis-related genes, SSII and Wx, in endosperm - Lichun Huang; Zhengwen Gu; Zhuanzhuan Chen; Jiawen Yu; Rui Chu; Hongyan Tan; Dongsheng Zhao; Xiaolei Fan; Changquan Zhang; Qianfeng Li; Qiaoquan Liu (Plant Molecular Biology, 2021)

Coupling loss characteristics of N-P-C through runoff and sediment in the hilly region of SE China under simulated rainfall - Longzhou Deng; Tianyu Sun; Kai Fei; Liping Zhang; Xiaojuan Fan; Yanhong Wu; Liang Ni; Rui Sun (Environmental Science and Pollution Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Somatic embryogenesis of masson pine (Pinus massoniana): initiation, maturation and genetic stability analysis at SSR loci - Xin-Rui Xia; Fan Yang; Xin Ke; You-Mei Chen; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Unraveling Street-Level Air Pollution upon a Pivotal City of Yangtze River Delta, China - Rui Feng; Han Gao; Zhuo Wang; Kun Luo; Jian-ren Fan; Hui-jun Zheng (Aerosol Science and Engineering, 2021)

Precise frequency transfer model suitable for short baseline link based on GPS single-differenced observations with ambiguity resolution - Rui Tu; Pengfei Zhang; Rui Zhang; Lihong Fan; Junqiang Han; Ju Hong; Jinhai Liu; Xiaochun Lu (Acta Geodaetica et Geophysica, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Sleep quality and mental health of medical workers during the coronavirus disease 2019 pandemic - Yahua Zheng; Lili Wang; Lingfei Feng; Lingxiao Ye; Aiping Zhang; Rui Fan (Sleep and Biological Rhythms, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Association Between Blood Heavy Metal Concentrations and Dyslipidemia in the Elderly - Xingmeng Zhu; Yong Fan; Jie Sheng; Ling Gu; Qi Tao; Rui Huang; Kaiyong Liu; Linsheng Yang; Guimei Chen; Hongjuan Cao; Kaichun Li; Fangbiao Tao; et al. (Biological Trace Element Research, 2021)

Uncertainty Visualisation of a 3D Geological Geometry Model and Its Application in GIS-Based Mineral Resource Assessment: A Case Study in Huayuan District, Northwestern Hunan Province, China - Nan Li; Cangbai Li; Wenkai Chu; Keyan Xiao; Weihan Tao; Xianglong Song; Rui Cao; Yang Xu; Mingjing Fan (Journal of Earth Science, 2021)

Aerobic degradation of 4-fluoroaniline and 2,4-difluoroaniline: performance and microbial community in response to the inocula - Zhi-Qing Zhao; Xiao-Meng Wei; Xiao-Li Shen; Ghulam Abbas; Rui Fan; Yi Jin (Biodegradation, 2021)

Stress analysis of subsea risers under the combined action of wave force and seismic wave - Dongfeng Li; Shangyu Yang; Heng Fan; Rui Wang; Xiangzhen Yan (Arabian Journal of Geosciences, 2021)

Aerosolization Performance, Antitussive Effect and Local Toxicity of Naringenin-Hydroxypropyl-β-Cyclodextrin Inhalation Solution for Pulmonary Delivery - Minyi Guan; Xuan Zeng; Rui Shi; Yuying Zheng; Weiyang Fan; Weiwei Su (AAPS PharmSciTech, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Neonatal curcumin treatment restores hippocampal neurogenesis and improves autism-related behaviors in a mouse model of autism - Hongyu Zhong; Rui Xiao; Ruotong Ruan; Hui Liu; Xin Li; Yun Cai; Jinghui Zhao; Xiaotang Fan (Psychopharmacology, 2020)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Somatic embryogenesis in slash pine (Pinus elliottii Engelm): improving initiation of embryogenic tissues and maturation of somatic embryos - Fan Yang; Xin-Rui Xia; Xin Ke; Jianren Ye; Li-hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Infrared microthermometry of fluid inclusions in transparent to opaque minerals: challenges and new insights - Hong-Wei Peng; Hong-Rui Fan; M. Santosh; Fang-Fang Hu; Peng Jiang (Mineralium Deposita, 2020)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Spatio-temporal characteristics of the relationship between carbon emissions and economic growth in China’s transportation industry - Li Wang; Jie Fan; Jiaoyue Wang; Yanfei Zhao; Zhen Li; Rui Guo (Environmental Science and Pollution Research, 2020)

A model to obtain timing solution with un-differenced observations suitable for single-station/multi-station, a case study of BDS data - Pengfei Zhang; Rui Tu; Rui Zhang; Junqiang Han; Lihong Fan (Acta Geodaetica et Geophysica, 2020)

Reductions in water, soil and nutrient losses and pesticide pollution in agroforestry practices: a review of evidence and processes - Xiai Zhu; Wenjie Liu; Jin Chen; L. Adrian Bruijnzeel; Zhun Mao; Xiaodong Yang; Rémi Cardinael; Fan-Rui Meng; Roy C. Sidle; Steffen Seitz; Vimala D. Nair; Kazuki Nanko; et al. (Plant and Soil, 2020)

Decoding Tropospheric Ozone in Hangzhou, China: from Precursors to Sources - Rui Feng; Kun Luo; Jian-ren Fan (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Change detection in very high-resolution images based on ensemble CNNs - Xinlong Zhang; Rui Fan; Lei Ma; Xiaohan Liao; Xiuwan Chen (International Journal of Remote Sensing, 2020)

Protective effect of apigenin on d-galactosamine/LPS-induced hepatocellular injury by increment of Nrf-2 nucleus translocation - Rui-Jun Zhou; Ying Zhao; Ke Fan; Mei-Lin Xie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Quality dependence of litter decomposition and its carbon, nitrogen and phosphorus release under simulated acid rain treatments - Hui Wei; Rui Ma; Jiaen Zhang; Leyi Zhou; Ziqiang Liu; Zhenyi Fan; Jiayue Yang; Xiaoran Shan; Huimin Xiang (Environmental Science and Pollution Research, 2020)

Structural Networks Constraints on Alteration and Mineralization Processes in the Jiaojia Gold Deposit, Jiaodong Peninsula, China - Huanlong Hu; Shuangliang Liu; Hong-Rui Fan; Kuifeng Yang; Yabin Zuo; Yachun Cai (Journal of Earth Science, 2020)

Late Early-Cretaceous Magma Mixing in the Langqi Island, Fujian Province, China: Evidences from Petrology, Geochemistry and Zircon Geochronology - Liangliang Huang; Liyuan Wang; Hong-Rui Fan; Musen Lin; Wenhui Zhang (Journal of Earth Science, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Detection performance of azimuthal electromagnetic logging while drilling tool in anisotropic media - Zhen-Guan Wu; Lei Wang; Yi-Ren Fan; Shao-Gui Deng; Rui Huang; Tao Xing (Applied Geophysics, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Geochronological and sulfur isotopic evidence for the genesis of the post-magmatic, deeply sourced, and anomalously gold-rich Daliuhang orogenic deposit, Jiaodong, China - Kai Feng; Hong-Rui Fan; David I. Groves; Kui-Feng Yang; Fang-Fang Hu; Xuan Liu; Ya-Chun Cai (Mineralium Deposita, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Evaluation of Inoculum Sources for Aerobic Treatment of 2,3,4-Trifluoroaniline During Start-up and Shock - Zhi-Qing Zhao; Xiao-Li Shen; Tu-Cai Zheng; Ghulam Abbas; Rui Fan; Yan-Mei Li (Water, Air, & Soil Pollution, 2019)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

An improved method for detecting BeiDou signal-in-space anomalies from precise ephemerides - Lihong Fan; Rui Tu; Rui Zhang; Zengji Zheng; Xiaochun Lu; Jinhai Liu; Xiaodong Huang; Ju Hong (Acta Geodaetica et Geophysica, 2019)

Evaluation of Liquefaction Potential in Saturated Sand under Different Drainage Boundary Conditions—An Energy Approach - Chang-Rui Yao; Bo Wang; Zhi-Qiang Liu; Hao Fan; Fang-Hao Sun; Xin-Hao Chang (Journal of Marine Science and Engineering, 2019)
Drainage conditions are supposed to have significant influence on sand liquefaction behavior. An infiltration device was utilized in cyclic triaxial tests to reproduce different drainage conditions by altering dry density of the within silt. Permeability coefficient ratio (kp) was utilized for quantifying the drainage boundary effect. Cyclic triaxial tests were conducted on saturated Fujian standard sand samples. Test results were used to evaluate the liquefaction potential by using the energy approach. It can be concluded that, if kp increases slightly bigger than zero, excess pore water pressure (EPWP) will respond more fiercely, and the dissipated energy that triggers sand liquefaction will be less. By considering kp, an energy-based database was built by taking kp into consideration and different neural network (NN) models were constructed to predict liquefaction potential by energy approaches accurately under different drainage boundary conditions. It was suggested that the neuro-fuzzy (NF)-based NN model has more satisfactory performance.

Filler improvement and purification effects of constructed rapid infiltration facility - Rui-song Zhao; Jia-ke Li; Chao Guo; Fan Li; Huai-en Li (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

Effects of frequency and confining pressure on consolidation drainage behavior of soft marine clays - Yong-Hong Miao; Fan-Bo Zhou; Jie Yin; Yan-Chang Sun; Rui-Bing Li; Jian-Fei Lu (Marine Georesources & Geotechnology, 2019)

Ethylene, xylene, toluene and hexane are major contributors of atmospheric ozone in Hangzhou, China, prior to the 2022 Asian Games - Rui Feng; Qing Wang; Cheng-chen Huang; Jin Liang; Kun Luo; Jian-ren Fan; Hui-jun Zheng (Environmental Chemistry Letters, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Neonatal exposure to propofol affects interneuron development in the piriform cortex and causes neurobehavioral deficits in adult mice - Dan Yu; Rui Xiao; Jing Huang; Yulong Cai; Xiaohang Bao; Sheng Jing; Zhiyong Du; Tiande Yang; Xiaotang Fan (Psychopharmacology, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Effects of resveratrol on regulation on UCP2 and cardiac function in diabetic rats - Jiayu Diao; Jin Wei; Rui Yan; Gang Fan; Lin Lin; Mengjie Chen (Journal of Physiology and Biochemistry, 2019)

Pyrite textures and compositions from the Zhuangzi Au deposit, southeastern North China Craton: implication for ore-forming processes - Xing-Hui Li; Hong-Rui Fan; Kui-Feng Yang; Pete Hollings; Xuan Liu; Fang-Fang Hu; Ya-Chun Cai (Contributions to Mineralogy and Petrology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Geochronology, geochemistry, and Sr–Nd–Pb–Hf isotopes of the Zhunsujihua granitoid intrusions associated with the molybdenum deposit, northern Inner Mongolia, China: implications for petrogenesis and tectonic setting - Xiaojun Zhang; David R. Lentz; Chunliang Yao; Rui Liu; Zhen Yang; Yanxiong Mei; Xianwang Fan; Fei Huang; Ying Qin; Kun Zhang; Zhenfei Zhang (International Journal of Earth Sciences, 2018)

Effect of nanoparticle hydroxyapatite on the immobilization of Cu and Zn in polluted soil - Rui-Juan Sun; Jie-Hua Chen; Ting-Ting Fan; Dong-Mei Zhou; Yu-Jun Wang (Environmental Science and Pollution Research, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Nominal effective immunoreaction volume of magnetic beads at single bead level - Rui Wang; Yuan Chen; Kai Fan; Feng Ji; Jian Wu; Yong-hua Yu (Journal of Zhejiang University-SCIENCE B, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Genome editing in potato plants by agrobacterium-mediated transient expression of transcription activator-like effector nucleases - Jin Ma; Heng Xiang; Danielle J. Donnelly; Fan-Rui Meng; Huimin Xu; Dion Durnford; Xiu-Qing Li (Plant Biotechnology Reports, 2017)

SWAT Setup with Long-Term Detailed Landuse and Management Records and Modification for a Micro-Watershed Influenced by Freeze-Thaw Cycles - Junyu Qi; Sheng Li; Qi Yang; Zisheng Xing; Fan-Rui Meng (Water Resources Management, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Study on Enhanced Dissolution of Azilsartan-Loaded Solid Dispersion, Prepared by Combining Wet Milling and Spray-Drying Technologies - Tianshu Lu; Yinghua Sun; Dawei Ding; Qi Zhang; Rui Fan; Zhonggui He; Jing Wang (AAPS PharmSciTech, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Assessing an Enhanced Version of SWAT on Water Quantity and Quality Simulation in Regions with Seasonal Snow Cover - Junyu Qi; Sheng Li; Qiang Li; Zisheng Xing; Charles P.-A. Bourque; Fan-Rui Meng (Water Resources Management, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Projecting In-stream Dissolved Organic Carbon and Total Mercury Concentrations in Small Watersheds Following Forest Growth and Clearcutting - Chengfu Zhang; Rob C. Jamieson; Fan-Rui Meng; Robert Gordon; Charles P.-A. Bourque (Water, Air, & Soil Pollution, 2016)

PLD3 in Alzheimer’s Disease: a Modest Effect as Revealed by Updated Association and Expression Analyses - Deng-Feng Zhang; Yu Fan; Dong Wang; Rui Bi; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

A Novel Chromone Schiff-Base Fluorescent Chemosensor for Cd(II) Based on C=N Isomerization - Jun Yan; Long Fan; Jing-can Qin; Chao-rui Li; Zheng-yin Yang (Journal of Fluorescence, 2016)

Reconstruction of historical lead contamination and sources in Lake Hailing, Eastern China: a Pb isotope study - Rui Zhang; Minglei Guan; Yujie Shu; Liya Shen; Xixi Chen; Fan Zhang; Tiegang Li; Tingchen Jiang (Environmental Science and Pollution Research, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Geological and geochronological constraints on the genesis of the giant Tongkuangyu Cu deposit (Palaeoproterozoic), North China Craton - Xuan Liu; Hong-Rui Fan; M. Santosh; Kui-Feng Yang; Zheng-Jie Qiu; Fang-Fang Hu; Bo-Jie Wen (International Geology Review, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

The processes of graft union formation in tomato - Jingwei Fan; Rui Yang; Xiaoman Li; Wenchao Zhao; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Prioritizing Genes Related to Nicotine Addiction Via a Multi-source-Based Approach - Xinhua Liu; Meng Liu; Xia Li; Lihua Zhang; Rui Fan; Ju Wang (Molecular Neurobiology, 2015)

Protective enzymes and genes related to the JA pathway are involved in the response to root-knot nematodes at high soil temperatures in tomatoes carrying Mi-1 - Canli Hu; Wenchao Zhao; Jingwei Fan; Zilong Li; Rui Yang; Fukuan Zhao; JianLi Wang; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Effects of light intensity and quality on phycobiliprotein accumulation in the cyanobacterium Nostoc sphaeroides Kützing - Rui Ma; Fan Lu; Yonghong Bi; Zhengyu Hu (Biotechnology Letters, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

MTBP inhibits migration and metastasis of hepatocellular carcinoma - Qian Bi; Atul Ranjan; Rui Fan; Neeraj Agarwal; Danny R. Welch; Steven A. Weinman; Jie Ding; Tomoo Iwakuma (Clinical & Experimental Metastasis, 2015)

Estimation of potential impacts of climate change on growth and yield of temperate tree species - M. Irfan Ashraf; Charles P.-A. Bourque; David A. MacLean; Thom Erdle; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2015)

Advances in investigations on the mechanism of cancer multidrug resistance and the liposomes-based treatment strategy - Fan Zeng; Rui-Jun Ju; Xue-Tao Li; Wan-Liang Lu (Journal of Pharmaceutical Investigation, 2014)

Cooling and exhumation of the mid-Jurassic porphyry copper systems in Dexing City, SE China: insights from geo- and thermochronology - Xuan Liu; Hong-rui Fan; Noreen J. Evans; Geoffrey E. Batt; Brent I. A. McInnes; Kui-feng Yang; Ke-zhang Qin (Mineralium Deposita, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

How do soil and water conservation practices influence climate change impacts on potato production? Evidence from eastern Canada - Thomas O. Ochuodho; Edward Olale; Van A. Lantz; Jerome Damboise; Jean-Louis Daigle; Fan-Rui Meng; Sheng Li; T. Lien Chow (Regional Environmental Change, 2014)

Origin of sanukitoid and hornblendite enclaves in the Dajitu pluton from the Yinshan Block, North China Craton: product of Neoarchaean ridge subduction? - Xudong Ma; Hong-Rui Fan; M. Santosh; Xuan Liu; Jing-Hui Guo (International Geology Review, 2014)

Precise and Economical Dredging Model of Sediments and Its Field Application: Case Study of a River Heavily Polluted by Organic Matter, Nitrogen, and Phosphorus - Rui Zhang; Fan-Xin Zeng; Wu-Jun Liu; Raymond J. Zeng; Hong Jiang (Environmental Management, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Origin of the Yinshan epithermal-porphyry Cu–Au–Pb–Zn–Ag deposit, southeastern China: insights from geochemistry, Sr–Nd and zircon U–Pb–Hf–O isotopes - Xuan Liu; Hong-Rui Fan; M. Santosh; Fang-Fang Hu; Kui-Feng Yang; Bo-Jie Wen; Yue-Heng Yang; Yongsheng Liu (International Geology Review, 2013)

Geochemistry and zircon U–Pb chronology of charnockites in the Yinshan Block, North China Craton: tectonic evolution involving Neoarchaean ridge subduction - Xudong Ma; Hong-Rui Fan; M. Santosh; Jinghui Guo (International Geology Review, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Depletion of histone demethylase KDM2A inhibited cell proliferation of stem cells from apical papilla by de-repression of p15INK4B and p27Kip1 - Runtao Gao; Rui Dong; Juan Du; Ping Ma; Songlin Wang; Zhipeng Fan (Molecular and Cellular Biochemistry, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Trichoderma biodiversity in China - Rui-yan Sun; Zhi-cheng Liu; Kehe Fu; Lili Fan; Jie Chen (Journal of Applied Genetics, 2012)

Phosphorylation of GIT1 tyrosine 321 is required for association with FAK at focal adhesions and for PDGF-activated migration of osteoblasts - Yongxin Ren; Lipeng Yu; Jin Fan; Ze Rui; Zhengzhe Hua; Zitao Zhang; Ning Zhang; Guoyong Yin (Molecular and Cellular Biochemistry, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Proteomic analysis of seed germination under salt stress in soybeans - Xiao-yan Xu; Rui Fan; Rui Zheng; Chun-mei Li; De-yue Yu (Journal of Zhejiang University-SCIENCE B, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

The role of diurnal cycle in subduction/obduction - Ling Ling Liu; Rui Xin Huang; Fan Wang (Journal of Oceanography, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Possible influence of Arctic Oscillation on dust storm frequency in North China - Rui Mao; Daoyi Gong; Jingdong Bao; Yida Fan (Journal of Geographical Sciences, 2011)

The Qiyugou gold-bearing breccia pipes, Xiong'ershan region, central China: fluid-inclusion and stable-isotope evidence for an origin from magmatic fluids - Hong-Rui Fan; Fang-Fang Hu; Simon A. Wilde; Kui-Feng Yang; Chen-Wei Jin (International Geology Review, 2011)

A stand dynamic model for red pine plantations with different initial densities - Shusheng Li; Qingyu Hao; Edwin Swift; Charles P.-A. Bourque; Fan-Rui Meng (New Forests, 2011)

Erratum to: Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

A possible role of myristoylated alanine-rich C kinase substrate in endocytic pathway of Alzheimer’s disease - Rui Su; Zhen-Yun Han; Ji-Ping Fan; Yun-Ling Zhang (Neuroscience Bulletin, 2010)

Radiosonde observations of high-latitude planetary waves in the lower atmosphere - Rui Wang; ShaoDong Zhang; Fan Yi (Science China Earth Sciences, 2010)

Impacts of Accuracy and Resolution of Conventional and LiDAR Based DEMs on Parameters Used in Hydrologic Modeling - Zhengyong Zhao; Glenn Benoy; Thien Lien Chow; Herb W. Rees; Jean-Louis Daigle; Fan-Rui Meng (Water Resources Management, 2010)

Assessing impact of projected future climate on tree species growth and yield: development of an evaluation strategy - Shaun Dombroskie; Monica McKendy; Courtney Ruelland; William Richards; Charles P.-A. Bourque; Fan-Rui Meng (Mitigation and Adaptation Strategies for Global Change, 2010)

Characterization of the Photosynthetic Apparatus and Proteome of Roseobacter denitrificans - Kai Tang; Rui Zong; Fan Zhang; Na Xiao; Nianzhi Jiao (Current Microbiology, 2010)

Identification and Expression Pattern of a Novel NAM, ATAF, and CUC-Like Gene from Citrus sinensis Osbeck - Yong-Zhong Liu; M. N. R. Baig; Rui Fan; Jun-Li Ye; Yin-Chuan Cao; Xiu-Xin Deng (Plant Molecular Biology Reporter, 2009)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Molecular characterization of grapevine yellow speckle viroid-2 (GYSVd-2) - Dongmei Jiang; Zhixiang Zhang; Zujian Wu; Rui Guo; Hongqing Wang; Peige Fan; Shifang Li (Virus Genes, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Effects of Cations and PH on Antimicrobial Activity of Thanatin and s-Thanatin Against Escherichia coli ATCC25922 and B. subtilis ATCC 21332 - Guoqiu Wu; Jiaxuan Ding; Hui Li; Linxian Li; Rui Zhao; Zilong Shen; Xiaobo Fan; Tao Xi (Current Microbiology, 2008)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

East Asian dust storm and weather disturbance: possible links to the Arctic Oscillation - Dao‐Yi Gong; Rui Mao; Yi‐Da Fan (International Journal of Climatology, 2006)
In this work, the authors investigated the spring dust storm frequency variations in northern China and its relationship with weather disturbances, cold high, eddy kinetic energy (EKE), as well as the impact of the Arctic Oscillation (AO) on the dust storm frequency variations. It is found that there is a significantly decreasing trend of −26%/10 years in the dust storm frequency variations. In addition, the year‐to‐year variations are also remarkable, which account for 58.3% of the total variance of the dust storm frequency variations. The synoptic variance of 850 hPa height, EKE, and near‐surface cold highs are highly correlated with the dust storm frequency variations. During the last 40 years or so, there have been significant trends in synoptic variance, cold‐high frequency, and kinetic energy over northern China and Mongolia, which are −3.2, −4.0, and −5.0%/10 years, respectively. The trends are fairly consistent with long‐term variations of dust storm frequency. The AO shows good correlation with the interannual variations of the dust storm frequency. This out‐of‐phase relation is supported by the significantly negative correlations between AO index and eddy growth rate between 850/700 hPa in midlatitude East Asia, implying that AO can modulate weather disturbances and dust storm activities through influencing the atmospheric instability. It is found, however, that the spring AO index shows no evident long‐term trend. Land cover changes, global warming, and other climate teleconnections may, at least partly, be responsible for the secular decreasing of dust storm frequency over northern China. Copyright © 2006 Royal Meteorological Society.

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Spatial extent of winter thaw events in eastern North America: historical weather records in relation to yellow birch decline - Charles P.‐A. Bourque; Roger M. Cox; Darren J. Allen; Paul A. Arp; Fan‐Rui Meng (Global Change Biology, 2005)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Combining carbon sequestration objectives with timber management planning - Fan-Rui Meng; Charles P.-A. Bourque; Steven P. Oldford; D. Edwin Swift; Helen C. Smith (Mitigation and Adaptation Strategies for Global Change, 2003)

Ore-forming fluids associated with granite-hosted gold mineralization at the Sanshandao deposit, Jiaodong gold province, China - Hong Rui Fan; Ming Guo Zhai; Yi Han Xie; Jin Hui Yang (Mineralium Deposita, 2003)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Evaluating Critical Soil Acidification Loads and Exceedances for a Deciduous Forest at the Turkey Lakes Watershed - Mohammed Moayeri; Fan-Rui Meng; Paul A. Arp; Neil W. Foster (Ecosystems, 2001)

A New Height Growth Model for Dominant and Codominant Trees - Fan-Rui Meng; Chao Ho Meng; Shouzheng Tang; Paul A. Arp (Forest Science, 1997)
A model was developed to predict height growth for dominant and codominant trees, using asymptotic tree height, and tree height at the age of maximum height growth as principal characteristics to express the influence of site on tree height. The proposed model has many desirable attributes: it (1) produces polymorphic site-index curves, (2) contains an inflection point, (3) asymptotically approaches maximum tree height as age increases, (4) is mathematically defined at the point of origin, and (5) has a theoretical base (pipe model theory) for height growth. Model performance was evaluated with stem analysis data taken from naturally regenerated forest stands of mature to overmature balsam fir (Abies balsamea [L.] Mill.) and black spruce (Picea mariana Mill.) growing in two separate regions within New Brunswick, Canada. The model was also evaluated by analyzing its ability to reproduce existing site index curves for red pine (Pinus resinosa Ait.). The results indicate that the proposed model performs slightly better than an existing 5-parameter model based on the Richards' growth function. For. Sci. 43(3):348-354.